Association of De Novo Variants With Childhood Onset Moyamoya Disease and Diffuse Occlusive Vasculopathy. - Pinard, Amelie; Fiander, Maximillian D J; Cecchi, Alana C; Rideout, Andrea L; Azouz, Mohamed; Fraser, Stuart M; McNeely, P Daniel; Walling, Simon; Novara, Sarah C; Hurst, Anna C E; Guo, Dongchuan; Parkash, Sandhya; et al. (Neurology, 2021)
OBJECTIVE: To test the hypothesis that de novo genetic variants are responsible for moyamoya disease (MMD) in children with unaffected relatives, we performed exome sequencing of 28 affected children and their unaffected parents. METHODS: Exome sequencing was performed on 28 trios of affected patients with MMD and unaffected parents. RESULTS: We identified 3 novel rare de novo variants, 1 in the RING domain and 2 in a highly conserved region distal to the RING domain (4,114-4,120). These de novo cases of MMD present at a young age with aggressive MMD and uniquely have additional occlusive vascular lesions, including renal artery stenosis. Two previously reported cases had de novo variants in the same limited region and presented young with aggressive MMD, and 1 case had narrowing of the inferior abdominal aorta. CONCLUSIONS: These results indicate a novel syndrome associated with rare variants defined by de novo mutations disrupting highly conserved amino acids in the RING domain and a discrete region distal to the RING domain delimited by amino acids 4,114 to 4,120 leading to onset of severe MMD before 3 years of age and occlusion of other arteries, including the abdominal aorta, renal, iliac, and femoral arteries.
Keywords: Adenosine Triphosphatases; Adult; Age of Onset; Aortic Diseases; Arterial Occlusive Diseases; Child, Preschool; Female; Femoral Artery; Humans; Iliac Artery; Male; Moyamoya Disease; Mutation; Renal Artery Obstruction; Ubiquitin-Protein Ligases

Deletion of CTCF sites in the SHH locus alters enhancer-promoter interactions and leads to acheiropodia. - Ushiki, Aki; Zhang, Yichi; Xiong, Chenling; Zhao, Jingjing; Georgakopoulos-Soares, Ilias; Kane, Lauren; Jamieson, Kirsty; Bamshad, Michael J; Nickerson, Deborah A; Shen, Yin; Lettice, Laura A; Silveira-Lucas, Elizabeth Lemos; et al. (Nat Commun, 2021)
Acheiropodia, congenital limb truncation, is associated with homozygous deletions in the LMBR1 gene around ZRS, an enhancer regulating SHH during limb development. How these deletions lead to this phenotype is unknown. Using whole-genome sequencing, we fine-mapped the acheiropodia-associated region to 12 kb and show that it does not function as an enhancer. CTCF and RAD21 ChIP-seq together with 4C-seq and DNA FISH identify three CTCF sites within the acheiropodia-deleted region that mediate the interaction between the ZRS and the SHH promoter. This interaction is substituted with other CTCF sites centromeric to the ZRS in the disease state. Mouse knockouts of the orthologous 12 kb sequence have no apparent abnormalities, showcasing the challenges in modelling CTCF alterations in animal models due to inherent motif differences between species. Our results show that alterations in CTCF motifs can lead to a Mendelian condition due to altered enhancer-promoter interactions.
Keywords: Animals; Binding Sites; CCCTC-Binding Factor; Chromatin Immunoprecipitation Sequencing; Disease Models, Animal; Embryo, Mammalian; Enhancer Elements, Genetic; Exons; Extremities; Female; Foot Deformities, Congenital; Gene Expression Regulation, Developmental; Genetic Loci; Genetic Testing; Hand Deformities, Congenital; Hedgehog Proteins; Humans; Introns; Male; Membrane Proteins; Mice; Mice, Knockout; Promoter Regions, Genetic; Sequence Deletion; Species Specificity; Whole Genome Sequencing

8q24 genetic variation and comprehensive haplotypes altering familial risk of prostate cancer. - Dupont, William D; Breyer, Joan P; Plummer, W Dale; Chang, Sam S; Cookson, Michael S; Smith, Joseph A; Blue, Elizabeth E; Bamshad, Michael J; Smith, Jeffrey R (Nat Commun, 2020)
The 8q24 genomic locus is tied to the origin of numerous cancers. We investigate its contribution to hereditary prostate cancer (HPC) in independent study populations of the Nashville Familial Prostate Cancer Study and International Consortium for Prostate Cancer Genetics (combined: 2,836 HPC cases, 2,206 controls of European ancestry). Here we report 433 variants concordantly associated with HPC in both study populations, accounting for 9% of heritability and modifying age of diagnosis as well as aggressiveness; 183 reach genome-wide significance. The variants comprehensively distinguish independent risk-altering haplotypes overlapping the 648 kb locus (three protective, and four risk (peak odds ratios: 1.5, 4, 5, and 22)). Sequence of the near-Mendelian haplotype reveals eleven causal mutation candidates. We introduce a linkage disequilibrium-based algorithm discerning eight independent sentinel variants, carrying considerable risk prediction ability (AUC = 0.625) for a single locus. These findings elucidate 8q24 locus structure and correlates for clinical prediction of prostate cancer risk.
Keywords: Aged; Case-Control Studies; Chromosomes, Human, Pair 8; European Continental Ancestry Group; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Haplotypes; Heterozygote; Humans; Linkage Disequilibrium; Male; Middle Aged; Mutation; Prostatic Neoplasms; Protective Factors; Risk Factors

De novo and inherited variants in ZNF292 underlie a neurodevelopmental disorder with features of autism spectrum disorder. - Mirzaa, Ghayda M; Chong, Jessica X; Piton, Amélie; Popp, Bernt; Foss, Kimberly; Guo, Hui; Harripaul, Ricardo; Xia, Kun; Scheck, Joshua; Aldinger, Kimberly A; Sajan, Samin A; Tang, Sha; et al. (Genet Med, 2020)
PURPOSE: Intellectual disability (ID) and autism spectrum disorder (ASD) are genetically heterogeneous neurodevelopmental disorders. We sought to delineate the clinical, molecular, and neuroimaging spectrum of a novel neurodevelopmental disorder caused by variants in the zinc finger protein 292 gene (ZNF292). METHODS: We ascertained a cohort of 28 families with ID due to putatively pathogenic ZNF292 variants that were identified via targeted and exome sequencing. Available data were analyzed to characterize the canonical phenotype and examine genotype-phenotype relationships. RESULTS: Probands presented with ID as well as a spectrum of neurodevelopmental features including ASD, among others. All ZNF292 variants were de novo, except in one family with dominant inheritance. ZNF292 encodes a highly conserved zinc finger protein that acts as a transcription factor and is highly expressed in the developing human brain supporting its critical role in neurodevelopment. CONCLUSION: De novo and dominantly inherited variants in ZNF292 are associated with a range of neurodevelopmental features including ID and ASD. The clinical spectrum is broad, and most individuals present with mild to moderate ID with or without other syndromic features. Our results suggest that variants in ZNF292 are likely a recurrent cause of a neurodevelopmental disorder manifesting as ID with or without ASD.
Keywords: Adolescent; Autism Spectrum Disorder; Carrier Proteins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Nerve Tissue Proteins; Neurodevelopmental Disorders; Neuroimaging; Whole Exome Sequencing

Dysfunction of the ciliary ARMC9/TOGARAM1 protein module causes Joubert syndrome. - Latour, Brooke L; Van De Weghe, Julie C; Rusterholz, Tamara Ds; Letteboer, Stef Jf; Gomez, Arianna; Shaheen, Ranad; Gesemann, Matthias; Karamzade, Arezou; Asadollahi, Mostafa; Barroso-Gil, Miguel; Chitre, Manali; Grout, Megan E; et al. (J Clin Invest, 2020)
Joubert syndrome (JBTS) is a recessive neurodevelopmental ciliopathy characterized by a pathognomonic hindbrain malformation. All known JBTS genes encode proteins involved in the structure or function of primary cilia, ubiquitous antenna-like organelles essential for cellular signal transduction. Here, we used the recently identified JBTS-associated protein armadillo repeat motif-containing 9 (ARMC9) in tandem-affinity purification and yeast 2-hybrid screens to identify a ciliary module whose dysfunction underlies JBTS. In addition to the known JBTS-associated proteins CEP104 and CSPP1, we identified coiled-coil domain containing 66 (CCDC66) and TOG array regulator of axonemal microtubules 1 (TOGARAM1) as ARMC9 interaction partners. We found that TOGARAM1 variants cause JBTS and disrupt TOGARAM1 interaction with ARMC9. Using a combination of protein interaction analyses, characterization of patient-derived fibroblasts, and analysis of CRISPR/Cas9-engineered zebrafish and hTERT-RPE1 cells, we demonstrated that dysfunction of ARMC9 or TOGARAM1 resulted in short cilia with decreased axonemal acetylation and polyglutamylation, but relatively intact transition zone function. Aberrant serum-induced ciliary resorption and cold-induced depolymerization in ARMC9 and TOGARAM1 patient cell lines suggest a role for this new JBTS-associated protein module in ciliary stability.
Keywords: Abnormalities, Multiple; Acetylation; Animals; Armadillo Domain Proteins; Cerebellum; Cilia; CRISPR-Cas Systems; Disease Models, Animal; Eye Abnormalities; Humans; Kidney Diseases, Cystic; Peptides; Retina; Zebrafish; Zebrafish Proteins

Further delineation of the clinical spectrum of KAT6B disorders and allelic series of pathogenic variants. - Zhang, Li Xin; Lemire, Gabrielle; Gonzaga-Jauregui, Claudia; Molidperee, Sirinart; Galaz-Montoya, Carolina; Liu, David S; Verloes, Alain; Shillington, Amelle G; Izumi, Kosuke; Ritter, Alyssa L; Keena, Beth; Zackai, Elaine; et al. (Genet Med, 2020)
PURPOSE: Genitopatellar syndrome and Say-Barber-Biesecker-Young-Simpson syndrome are caused by variants in the KAT6B gene and are part of a broad clinical spectrum called KAT6B disorders, whose variable expressivity is increasingly being recognized. METHODS: We herein present the phenotypes of 32 previously unreported individuals with a molecularly confirmed diagnosis of a KAT6B disorder, report 24 new pathogenic KAT6B variants, and review phenotypic information available on all published individuals with this condition. We also suggest a classification of clinical subtypes within the KAT6B disorder spectrum. RESULTS: We demonstrate that cerebral anomalies, optic nerve hypoplasia, neurobehavioral difficulties, and distal limb anomalies other than long thumbs and great toes, such as polydactyly, are more frequently observed than initially reported. Intestinal malrotation and its serious consequences can be present in affected individuals. Additionally, we identified four children with Pierre Robin sequence, four individuals who had increased nuchal translucency/cystic hygroma prenatally, and two fetuses with severe renal anomalies leading to renal failure. We also report an individual in which a pathogenic variant was inherited from a mildly affected parent. CONCLUSION: Our work provides a comprehensive review and expansion of the genotypic and phenotypic spectrum of KAT6B disorders that will assist clinicians in the assessment, counseling, and management of affected individuals.
Keywords: Blepharophimosis; Exons; Histone Acetyltransferases; Humans; Intellectual Disability; Mutation

MN1 C-terminal truncation syndrome is a novel neurodevelopmental and craniofacial disorder with partial rhombencephalosynapsis. - Mak, Christopher C Y; Doherty, Dan; Lin, Angela E; Vegas, Nancy; Cho, Megan T; Viot, Géraldine; Dimartino, Clémantine; Weisfeld-Adams, James D; Lessel, Davor; Joss, Shelagh; Li, Chumei; Gonzaga-Jauregui, Claudia; et al. (Brain, 2020)
MN1 encodes a transcriptional co-regulator without homology to other proteins, previously implicated in acute myeloid leukaemia and development of the palate. Large deletions encompassing MN1 have been reported in individuals with variable neurodevelopmental anomalies and non-specific facial features. We identified a cluster of de novo truncating mutations in MN1 in a cohort of 23 individuals with strikingly similar dysmorphic facial features, especially midface hypoplasia, and intellectual disability with severe expressive language delay. Imaging revealed an atypical form of rhombencephalosynapsis, a distinctive brain malformation characterized by partial or complete loss of the cerebellar vermis with fusion of the cerebellar hemispheres, in 8/10 individuals. Rhombencephalosynapsis has no previously known definitive genetic or environmental causes. Other frequent features included perisylvian polymicrogyria, abnormal posterior clinoid processes and persistent trigeminal artery. MN1 is encoded by only two exons. All mutations, including the recurrent variant p.Arg1295* observed in 8/21 probands, fall in the terminal exon or the extreme 3' region of exon 1, and are therefore predicted to result in escape from nonsense-mediated mRNA decay. This was confirmed in fibroblasts from three individuals. We propose that the condition described here, MN1 C-terminal truncation (MCTT) syndrome, is not due to MN1 haploinsufficiency but rather is the result of dominantly acting C-terminally truncated MN1 protein. Our data show that MN1 plays a critical role in human craniofacial and brain development, and opens the door to understanding the biological mechanisms underlying rhombencephalosynapsis.
Keywords: Abnormalities, Multiple; Adolescent; Basilar Artery; Carotid Arteries; Cerebellar Vermis; Cerebellum; Child; Child, Preschool; Cohort Studies; Comparative Genomic Hybridization; Craniofacial Abnormalities; Female; Fibroblasts; Humans; Imaging, Three-Dimensional; Infant; Intellectual Disability; Language Development Disorders; Magnetic Resonance Imaging; Male; Middle Aged; Mutation; Nervous System Malformations; Nonsense Mediated mRNA Decay; Polymicrogyria; Real-Time Polymerase Chain Reaction; RNA-Seq; Syndrome; Tomography, X-Ray Computed; Trans-Activators; Tumor Suppressor Proteins; Whole Exome Sequencing; Whole Genome Sequencing

Multi-omic studies on missense PLG variants in families with otitis media. - Bootpetch, Tori C; Hafrén, Lena; Elling, Christina L; Baschal, Erin E; Manichaikul, Ani W; Pine, Harold S; Szeremeta, Wasyl; Scholes, Melissa A; Cass, Stephen P; Larson, Eric D; Chan, Kenny H; Ishaq, Rafaqat; et al. (Sci Rep, 2020)
Otitis media (OM), a very common disease in young children, can result in hearing loss. In order to potentially replicate previously reported associations between OM and PLG, exome and Sanger sequencing, RNA-sequencing of saliva and middle ear samples, 16S rRNA sequencing, molecular modeling, and statistical analyses including transmission disequilibrium tests (TDT) were performed in a multi-ethnic cohort of 718 families and simplex cases with OM. We identified four rare PLG variants c.112A > G (p.Lys38Glu), c.782G > A (p.Arg261His), c.1481C > T (p.Ala494Val) and c.2045 T > A (p.Ile682Asn), and one common variant c.1414G > A (p.Asp472Asn). However TDT analyses for these PLG variants did not demonstrate association with OM in 314 families. Additionally PLG expression is very low or absent in normal or diseased middle ear in mouse and human, and salivary expression and microbial α-diversity were non-significant in c.1414G > A (p.Asp472Asn) carriers. Based on molecular modeling, the novel rare variants particularly c.782G > A (p.Arg261His) and c.2045 T > A (p.Ile682Asn) were predicted to affect protein structure. Exploration of other potential disease mechanisms will help elucidate how PLG contributes to OM susceptibility in humans. Our results underline the importance of following up findings from genome-wide association through replication studies, preferably using multi-omic datasets.
Keywords: Animals; Ear, Middle; Female; Genomics; Humans; Male; Mice; Microbiota; Mutation, Missense; Otitis Media; Pedigree; Plasminogen; Polymorphism, Single Nucleotide; Saliva

Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity

Mutations in MYLPF Cause a Novel Segmental Amyoplasia that Manifests as Distal Arthrogryposis. - Chong, Jessica X; Talbot, Jared C; Teets, Emily M; Previs, Samantha; Martin, Brit L; Shively, Kathryn M; Marvin, Colby T; Aylsworth, Arthur S; Saadeh-Haddad, Reem; Schatz, Ulrich A; Inzana, Francesca; Ben-Omran, Tawfeg; et al. (Am J Hum Genet, 2020)
We identified ten persons in six consanguineous families with distal arthrogryposis (DA) who had congenital contractures, scoliosis, and short stature. Exome sequencing revealed that each affected person was homozygous for one of two different rare variants (c.470G>T [p.Cys157Phe] or c.469T>C [p.Cys157Arg]) affecting the same residue of myosin light chain, phosphorylatable, fast skeletal muscle (MYLPF). In a seventh family, a c.487G>A (p.Gly163Ser) variant in MYLPF arose de novo in a father, who transmitted it to his son. In an eighth family comprised of seven individuals with dominantly inherited DA, a c.98C>T (p.Ala33Val) variant segregated in all four persons tested. Variants in MYLPF underlie both dominant and recessively inherited DA. Mylpf protein models suggest that the residues associated with dominant DA interact with myosin whereas the residues altered in families with recessive DA only indirectly impair this interaction. Pathological and histological exam of a foot amputated from an affected child revealed complete absence of skeletal muscle (i.e., segmental amyoplasia). To investigate the mechanism for this finding, we generated an animal model for partial MYLPF impairment by knocking out zebrafish mylpfa. The mylpfa mutant had reduced trunk contractile force and complete pectoral fin paralysis, demonstrating that mylpf impairment most severely affects limb movement. mylpfa mutant muscle weakness was most pronounced in an appendicular muscle and was explained by reduced myosin activity and fiber degeneration. Collectively, our findings demonstrate that partial loss of MYLPF function can lead to congenital contractures, likely as a result of degeneration of skeletal muscle in the distal limb.
Keywords: Adolescent; Amino Acid Sequence; Animals; Arthrogryposis; Child; Contracture; Extremities; Female; Humans; Male; Muscle, Skeletal; Musculoskeletal Abnormalities; Mutation; Myosin Light Chains; Myosins; Pedigree; Young Adult; Zebrafish

The pleiotropy associated with de novo variants in CHD4, CNOT3, and SETD5 extends to moyamoya angiopathy. - Pinard, Amelie; Guey, Stéphanie; Guo, Dongchuan; Cecchi, Alana C; Kharas, Natasha; Wallace, Stephanie; Regalado, Ellen S; Hostetler, Ellen M; Sharrief, Anjail Z; Bergametti, Françoise; Kossorotoff, Manoelle; Hervé, Dominique; et al. (Genet Med, 2020)
PURPOSE: Moyamoya angiopathy (MMA) is a cerebrovascular disease characterized by occlusion of large arteries, which leads to strokes starting in childhood. Twelve altered genes predispose to MMA but the majority of cases of European descent do not have an identified genetic trigger. METHODS: Exome sequencing from 39 trios were analyzed. RESULTS: We identified four de novo variants in three genes not previously associated with MMA: CHD4, CNOT3, and SETD5. Identification of additional rare variants in these genes in 158 unrelated MMA probands provided further support that rare pathogenic variants in CHD4 and CNOT3 predispose to MMA. Previous studies identified de novo variants in these genes in children with developmental disorders (DD), intellectual disability, and congenital heart disease. CONCLUSION: These genes encode proteins involved in chromatin remodeling, and taken together with previously reported genes leading to MMA-like cerebrovascular occlusive disease (YY1AP1, SMARCAL1), implicate disrupted chromatin remodeling as a molecular pathway predisposing to early onset, large artery occlusive cerebrovascular disease. Furthermore, these data expand the spectrum of phenotypic pleiotropy due to alterations of CHD4, CNOT3, and SETD5 beyond DD to later onset disease in the cerebrovascular arteries and emphasize the need to assess clinical complications into adulthood for genes associated with DD.
Keywords: Adult; Cell Cycle Proteins; Cerebrovascular Disorders; Child; Child, Preschool; Developmental Disabilities; DNA Helicases; Exome; Female; Genetic Predisposition to Disease; Humans; Intellectual Disability; Male; Methyltransferases; Mi-2 Nucleosome Remodeling and Deacetylase Complex; Middle Aged; Moyamoya Disease; Mutation; Nuclear Proteins; Transcription Factors; Whole Exome Sequencing

Rare deleterious variants of NOTCH1, GATA4, SMAD6, and ROBO4 are enriched in BAV with early onset complications but not in BAV with heritable thoracic aortic disease. - Musfee, Fadi I; Guo, Dongchuan; Pinard, Amélie C; Hostetler, Ellen M; Blue, Elizabeth E; Nickerson, Deborah A; Bamshad, Michael J; Milewicz, Dianna M; Prakash, Siddharth K (Mol Genet Genomic Med, 2020)
BACKGROUND: Bicuspid aortic valve (BAV) is the most common cardiovascular malformation in adults, with a prevalence of 0.5%-2%. The prevalence of BAV in cohorts who were ascertained due to thoracic aortic aneurysms or acute aortic dissections (TAD) is as high as 20%. However, the contribution of causal BAV genes to TAD is not known. Therefore, we evaluated rare deleterious variants of GATA4, NOTCH1, SMAD6, or ROBO4 in patients with BAV who presented with TAD. METHODS: Our cohort consisted of 487 probands with Heritable Thoracic Aortic Aneurysms or Dissections (HTAD, 12% BAV, 29% female) and 63 probands with Early onset complications of Bicuspid Aortic Valve disease (EBAV, 63% TAD, 34% female). After whole exome sequencing, we functionally annotated GATA4, NOTCH1, SMAD6, and ROBO4 variants and compared the prevalence of rare variants in these genes to controls without HTAD. RESULTS: We identified 11 rare deleterious variants of GATA4, SMAD6, or ROBO4 in 12 (18%) EBAV cases. The burden of rare SMAD6 and GATA4 variants was significantly enriched in EBAV but not in HTAD cases, even among HTAD cases with BAV (p < .003). CONCLUSION: Rare variants of NOTCH1, ROBO4, SMAD6, or GATA4 do not significantly contribute to BAV in cohorts with HTAD. We conclude that BAV patients who present with HTAD are a genetically distinct subgroup with implications for genetic testing and prognosis.
Keywords: Adult; Aortic Aneurysm, Thoracic; Bicuspid Aortic Valve Disease; Female; GATA4 Transcription Factor; Gene Frequency; Humans; Male; Middle Aged; Mutation; Receptor, Notch1; Receptors, Cell Surface; Smad6 Protein

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein-Taybi syndrome: the interconnections of epigenetic machinery disorders. - Negri, Gloria; Magini, Pamela; Milani, Donatella; Crippa, Milena; Biamino, Elisa; Piccione, Maria; Sotgiu, Stefano; Perrìa, Chiara; Vitiello, Giuseppina; Frontali, Marina; Boni, Antonella; Di Fede, Elisabetta; et al. (Hum Genet, 2019)
Rubinstein-Taybi syndrome (RSTS) is an autosomal-dominant neurodevelopmental disease affecting 1:125,000 newborns characterized by intellectual disability, growth retardation, facial dysmorphisms and skeletal abnormalities. RSTS is caused by mutations in genes encoding for writers of the epigenetic machinery: CREBBP (~ 60%) or its homologous EP300 (~ 10%). No causative mutation is identified in up to 30% of patients. We performed whole-exome sequencing (WES) on eight RSTS-like individuals who had normal high-resolution array CGH testing and were CREBBP- and EP300-mutation -negative, to identify the molecular cause. In four cases, we identified putatively causal variants in three genes (ASXL1, KMT2D and KMT2A) encoding members of the epigenetic machinery known to be associated with the Bohring-Opitz, Kabuki and Wiedemann-Steiner syndromes. Each variant is novel, de novo, fulfills the ACMG criteria and is predicted to result in loss-of-function leading to haploinsufficiency of the epi-gene. In two of the remaining cases, homozygous/compound heterozygous variants in XYLT2 and PLCB4 genes, respectively, associated with spondyloocular and auriculocondylar 2 syndromes and in the latter an additional candidate variant in XRN2, a gene yet unrelated to any disease, were detected, but their pathogenicity remains uncertain. These results underscore the broad clinical spectrum of Mendelian disorders of the epigenetic apparatus and the high rate of WES disclosure of the genetic basis in cases which may pose a challenge for phenotype encompassing distinct syndromes. The overlapping features of distinct intellectual disability syndromes reflect common pathogenic molecular mechanisms affecting the complex regulation of balance between open and closed chromatin.
Keywords: Child; Child, Preschool; Comparative Genomic Hybridization; CREB-Binding Protein; E1A-Associated p300 Protein; Epigenesis, Genetic; Facies; Female; Genetic Association Studies; Humans; Infant; Infant, Newborn; Male; Mutation; Phenotype; Rubinstein-Taybi Syndrome; Whole Exome Sequencing

Identification of CACNA1D variants associated with sinoatrial node dysfunction and deafness in additional Pakistani families reveals a clinical significance. - Liaqat, Khurram; Schrauwen, Isabelle; Raza, Syed Irfan; Lee, Kwanghyuk; Hussain, Shabir; Chakchouk, Imen; Nasir, Abdul; Acharya, Anushree; Abbe, Izoduwa; Umair, Muhammad; Ansar, Muhammad; Ullah, Irfan; et al. (J Hum Genet, 2019)
Sinoatrial node dysfunction and deafness (SANDD) syndrome is rare and characterized by a low heart beat and severe-to-profound deafness. Additional features include fatigue, dizziness, and episodic syncope. The sinoatrial node (SAN) drives heart automaticity and continuously regulates heart rate. The CACNA1D gene encoding the Ca1.3 protein expressed in inner hair cells, atria and SAN, induces loss-of-function in channel activity and underlies SANDD. To date, only one variant c.1208_1209insGGG:p.(G403_V404insG) has been reported for SANDD syndrome. We studied five Pakistani families with SANDD and characterized a new missense variant p.(A376V) in CACNA1D in one family, and further characterized the founder variant p.(G403_V404insG) in four additional pedigrees. We show that affected individuals in the four families which segregate p.(G403_V404insG) share a 1.03 MB haplotype on 3p21.1 suggesting they share a common distant ancestor. In conclusion, we identified new and known variants in CACNA1D in five Pakistani families with SANDD. This study is of clinical importance as the CACNA1D founder variant is only observed in families from the Khyber Pakhtunkhwa (KPK) province, in Pakistan. Therefore, screening patients with congenital deafness for SAN dysfunction in this province could ensure adequate follow-up and prevent cardiac failure associated with SAN.
Keywords: Adolescent; Calcium Channels, L-Type; Deafness; Female; Heart Diseases; Humans; Male; Mutation; Pakistan; Pedigree; Prognosis; Sinoatrial Node

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States; Whole Exome Sequencing

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly. - Ullah, Irfan; Kakar, Naseebullah; Schrauwen, Isabelle; Hussain, Shabir; Chakchouk, Imen; Liaqat, Khurram; Acharya, Anushree; Wasif, Naveed; Santos-Cortez, Regie Lyn P; Khan, Saadullah; Aziz, Abdul; Lee, Kwanghyuk; et al. (Hum Genet, 2019)
Postaxial polydactyly (PAP) is a common limb malformation that often leads to cosmetic and functional complications. Molecular evaluation of polydactyly can serve as a tool to elucidate genetic and signaling pathways that regulate limb development, specifically, the anterior-posterior specification of the limb. To date, only five genes have been identified for nonsyndromic PAP: FAM92A, GLI1, GLI3, IQCE and ZNF141. In this study, two Pakistani multiplex consanguineous families with autosomal recessive nonsyndromic PAP were clinically and molecularly evaluated. From both pedigrees, a DNA sample from an affected member underwent exome sequencing. In each family, we identified a segregating frameshift (c.591dupA [p.(Q198Tfs*21)]) and nonsense variant (c.2173A > T [p.(K725*)]) in KIAA0825 (also known as C5orf36). Although KIAA0825 encodes a protein of unknown function, it has been demonstrated that its murine ortholog is expressed during limb development. Our data contribute to the establishment of a catalog of genes important in limb patterning, which can aid in diagnosis and obtaining a better understanding of the biology of polydactyly.
Keywords: Animals; Consanguinity; Family Health; Female; Fingers; Genes, Recessive; Genetic Predisposition to Disease; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice, Inbred C57BL; Mutation; Pedigree; Phenotype; Polydactyly; Toes; Whole Exome Sequencing

Analyses of LMNA-negative juvenile progeroid cases confirms biallelic POLR3A mutations in Wiedemann-Rautenstrauch-like syndrome and expands the phenotypic spectrum of PYCR1 mutations. - Lessel, Davor; Ozel, Ayse Bilge; Campbell, Susan E; Saadi, Abdelkrim; Arlt, Martin F; McSweeney, Keisha Melodi; Plaiasu, Vasilica; Szakszon, Katalin; Szőllős, Anna; Rusu, Cristina; Rojas, Armando J; Lopez-Valdez, Jaime; et al. (Hum Genet, 2018)
Juvenile segmental progeroid syndromes are rare, heterogeneous disorders characterized by signs of premature aging affecting more than one tissue or organ starting in childhood. Hutchinson-Gilford progeria syndrome (HGPS), caused by a recurrent de novo synonymous LMNA mutation resulting in aberrant splicing and generation of a mutant product called progerin, is a prototypical example of such disorders. Here, we performed a joint collaborative study using massively parallel sequencing and targeted Sanger sequencing, aimed at delineating the underlying genetic cause of 14 previously undiagnosed, clinically heterogeneous, non-LMNA-associated juvenile progeroid patients. The molecular diagnosis was achieved in 11 of 14 cases (~ 79%). Furthermore, we firmly establish biallelic mutations in POLR3A as the genetic cause of a recognizable, neonatal, Wiedemann-Rautenstrauch-like progeroid syndrome. Thus, we suggest that POLR3A mutations are causal for a portion of under-diagnosed early-onset segmental progeroid syndromes. We additionally expand the clinical spectrum associated with PYCR1 mutations by showing that they can somewhat resemble HGPS in the first year of life. Moreover, our results lead to clinical reclassification in one single case. Our data emphasize the complex genetic and clinical heterogeneity underlying progeroid disorders.
Keywords: Adolescent; Alternative Splicing; Child; Female; Fetal Growth Retardation; Genetic Predisposition to Disease; Humans; Infant; Lamin Type A; Male; Mutation; Phenotype; Progeria; Pyrroline Carboxylate Reductases; RNA Polymerase III

Ari-1 Regulates Myonuclear Organization Together with Parkin and Is Associated with Aortic Aneurysms. - Tan, Kai Li; Haelterman, Nele A; Kwartler, Callie S; Regalado, Ellen S; Lee, Pei-Tseng; Nagarkar-Jaiswal, Sonal; Guo, Dong-Chuan; Duraine, Lita; Wangler, Michael F; Bamshad, Michael J; Nickerson, Deborah A; Lin, Guang; et al. (Dev Cell, 2018)
Nuclei are actively positioned and anchored to the cytoskeleton via the LINC (Linker of Nucleoskeleton and Cytoskeleton) complex. We identified mutations in the Parkin-like E3 ubiquitin ligase Ariadne-1 (Ari-1) that affect the localization and distribution of LINC complex members in Drosophila. ari-1 mutants exhibit nuclear clustering and morphology defects in larval muscles. We show that Ari-1 mono-ubiquitinates the core LINC complex member Koi. Surprisingly, we discovered functional redundancy between Parkin and Ari-1: increasing Parkin expression rescues ari-1 mutant phenotypes and vice versa. We further show that rare variants in the human homolog of ari-1 (ARIH1) are associated with thoracic aortic aneurysms and dissections, conditions resulting from smooth muscle cell (SMC) dysfunction. Human ARIH1 rescues fly ari-1 mutant phenotypes, whereas human variants found in patients fail to do so. In addition, SMCs obtained from patients display aberrant nuclear morphology. Hence, ARIH1 is critical in anchoring myonuclei to the cytoskeleton.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Animals; Aortic Aneurysm; Carrier Proteins; Cell Nucleus; Child, Preschool; Cytoskeleton; Drosophila melanogaster; Drosophila Proteins; Female; Humans; Male; Middle Aged; Mutation; Myocytes, Smooth Muscle; Pedigree; Phenotype; Ubiquitin-Protein Ligases; Young Adult

Confirmation of the Role of DHX38 in the Etiology of Early-Onset Retinitis Pigmentosa. - Latif, Zahid; Chakchouk, Imen; Schrauwen, Isabelle; Lee, Kwanghyuk; Santos-Cortez, Regie Lyn P; Abbe, Izoduwa; Acharya, Anushree; Jarral, Afeefa; Ali, Imran; Ullah, Ehsan; Khan, Muhammad Nasim; Ali, Ghazanfar; et al. (Invest Ophthalmol Vis Sci, 2018)
Purpose: Retinitis pigmentosa (RP) is a genetically heterogeneous trait with autosomal-recessive (ar) inheritance underlying 50% of genetic disease cases. Sixty-one arRP genes have been identified, and recently, DHX38 has been reported as a potential candidate gene for arRP with only a single family reported with a variant of unknown significance. We identified a missense variant in DHX38 that co-segregates with the arRP phenotype in two Pakistani families confirming the involvement of DHX38 in the etiology of early-onset RP. Methods: Exome sequencing was performed using two DNA samples from affected members of Pakistani families (MA88 and MA157) with early onset arRP. Sanger sequencing of DNA samples from all family members confirmed the segregation of candidate variant within both families. Results: A novel missense DHX38 variant c.971G>A; p.(Arg324Gln) was identified which segregates with the arRP phenotype and yielded a logarithm of the odds (LOD) score of 5.0 and 4.3 for families MA88 and MA157, respectively. This variant is predicted to be conserved and deleterious by several bioinformatics tools. Conclusions: We identified a second deleterious DHX38 variant that segregates with arRP in two families, providing additional evidence that DHX38 is involved in RP etiology. DHX38 encodes for pre-mRNA splicing factor PRP16, which is important in catalyzing pre-mRNA splicing.
Keywords: Adolescent; Adult; Cataract; Computational Biology; DEAD-box RNA Helicases; Female; Genes, Recessive; Genetic Association Studies; Genetic Linkage; Humans; Male; Mutation, Missense; Nucleotide Mapping; Ophthalmoscopy; Pedigree; Retinitis Pigmentosa; RNA Splicing Factors; Sequence Analysis, DNA; Whole Exome Sequencing; Young Adult

ERCC4 variants identified in a cohort of patients with segmental progeroid syndromes. - Mori, Takayasu; Yousefzadeh, Matthew J; Faridounnia, Maryam; Chong, Jessica X; Hisama, Fuki M; Hudgins, Louanne; Mercado, Gabriela; Wade, Erin A; Barghouthy, Amira S; Lee, Lin; Martin, George M; Nickerson, Deborah A; et al. (Hum Mutat, 2018)
Pathogenic variants in genes, which encode DNA repair and damage response proteins, result in a number of genomic instability syndromes with features of accelerated aging. ERCC4 (XPF) encodes a protein that forms a complex with ERCC1 and is required for the 5' incision during nucleotide excision repair. ERCC4 is also FANCQ, illustrating a critical role in interstrand crosslink repair. Pathogenic variants in this gene cause xeroderma pigmentosum, XFE progeroid syndrome, Cockayne syndrome (CS), and Fanconi anemia. We performed massive parallel sequencing for 42 unsolved cases submitted to the International Registry of Werner Syndrome. Two cases, each carrying two novel heterozygous ERCC4 variants, were identified. The first case was a compound heterozygote for: c.2395C > T (p.Arg799Trp) and c.388+1164_792+795del (p.Gly130Aspfs*18). Further molecular and cellular studies indicated that the ERCC4 variants in this patient are responsible for a phenotype consistent with a variant of CS. The second case was heterozygous for two variants in cis: c.[1488A > T; c.2579C > A] (p.[Gln496His; Ala860Asp]). While the second case also had several phenotypic features of accelerated aging, we were unable to provide biological evidence supporting the pathogenic roles of the associated ERCC4 variants. Precise genetic causes and disease mechanism of the second case remains to be determined.
Keywords: Actins; Aged; Cockayne Syndrome; DNA Repair; DNA-Binding Proteins; Fanconi Anemia; Female; Genetic Predisposition to Disease; Humans; Lamin Type A; Male; Middle Aged; Pedigree; Xeroderma Pigmentosum

LTBP3 Pathogenic Variants Predispose Individuals to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Pinard, Amelie; Chen, Jiyuan; Lee, Kwanghyuk; Rigelsky, Christina; Zilberberg, Lior; Hostetler, Ellen M; Aldred, Micheala; Wallace, Stephanie E; Prakash, Siddharth K; Leal, Suzanne M; et al. (Am J Hum Genet, 2018)
The major diseases affecting the thoracic aorta are aneurysms and acute dissections, and pathogenic variants in 11 genes are confirmed to lead to heritable thoracic aortic disease. However, many families in which multiple members have thoracic aortic disease do not have alterations in the known aortopathy genes. Genes highly expressed in the aorta were assessed for rare variants in exome sequencing data from such families, and compound rare heterozygous variants (p.Pro45Argfs25 and p.Glu750) in LTBP3 were identified in affected members of one family. A homozygous variant (p.Asn678_Gly681delinsThrCys) that introduces an additional cysteine into an epidermal growth factor (EGF)-like domain in the corresponding protein, latent TGF-β binding protein (LTBP-3), was identified in a second family. Individuals with compound heterozygous or homozygous variants in these families have aneurysms and dissections of the thoracic aorta, as well as aneurysms of the abdominal aorta and other arteries, along with dental abnormalities and short stature. Heterozygous carriers of the p.Asn678_Gly681delinsThrCys variant have later onset of thoracic aortic disease, as well as dental abnormalities. In these families, LTBP3 variants segregated with thoracic aortic disease with a combined LOD score of 3.9. Additionally, heterozygous rare LTBP3 variants were found in individuals with early onset of acute aortic dissections, and some of these variants disrupted LTBP-3 levels or EGF-like domains. When compared to wild-type mice, Ltbp3 mice have enlarged aortic roots and ascending aortas. In summary, homozygous LTBP3 pathogenic variants predispose individuals to thoracic aortic aneurysms and dissections, along with the previously described skeletal and dental abnormalities.
Keywords: Adult; Aged, 80 and over; Aneurysm, Dissecting; Animals; Aortic Aneurysm, Thoracic; Blood Pressure; Female; Genetic Predisposition to Disease; Homozygote; Humans; Latent TGF-beta Binding Proteins; Male; Mice; Middle Aged; Mutation; Pedigree

Monoallelic and biallelic CREB3L1 variant causes mild and severe osteogenesis imperfecta, respectively. - Keller, Rachel B; Tran, Thao T; Pyott, Shawna M; Pepin, Melanie G; Savarirayan, Ravi; McGillivray, George; Nickerson, Deborah A; Bamshad, Michael J; Byers, Peter H (Genet Med, 2018)
PurposeOsteogenesis imperfecta (OI) is a heritable skeletal dysplasia. Dominant pathogenic variants in COL1A1 and COL1A2 explain the majority of OI cases. At least 15 additional genes have been identified, but those still do not account for all OI phenotypes that present. We sought the genetic cause of mild and lethal OI phenotypes in an unsolved family.MethodsWe performed exome sequencing on seven members of the family, both affected and unaffected.ResultsWe identified a variant in cyclic AMP responsive element binding protein 3-like 1 (CREB3L1) in a consanguineous family. The variant caused a prenatal/perinatal lethal OI in homozygotes, similar to that seen in OI type II as a result of mutations in type I collagen genes, and a mild phenotype (fractures, blue sclerae) in multiple heterozygous family members. CREB3L1 encodes old astrocyte specifically induced substance (OASIS), an endoplasmic reticulum stress transducer. The variant disrupts a DNA-binding site and prevents OASIS from acting on its transcriptional targets including SEC24D, which encodes a component of the coat protein II complex.ConclusionThis report confirms that CREB3L1 is an OI-related gene and suggests the pathogenic mechanism of CREB3L1-associated OI involves the altered regulation of proteins involved in cellular secretion.
Keywords: Alleles; Amino Acid Sequence; Collagen Type I; Cyclic AMP Response Element-Binding Protein; DNA Mutational Analysis; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Mutation; Nerve Tissue Proteins; Osteogenesis Imperfecta; Pedigree; Phenotype; Radiography; Sequence Analysis, DNA; Severity of Illness Index; Ultrasonography, Prenatal

Mutations in the Epithelial Cadherin-p120-Catenin Complex Cause Mendelian Non-Syndromic Cleft Lip with or without Cleft Palate. - Cox, Liza L; Cox, Timothy C; Moreno Uribe, Lina M; Zhu, Ying; Richter, Chika T; Nidey, Nichole; Standley, Jennifer M; Deng, Mei; Blue, Elizabeth; Chong, Jessica X; Yang, Yueqin; Carstens, Russ P; et al. (Am J Hum Genet, 2018)
Non-syndromic cleft lip with or without cleft palate (NS-CL/P) is one of the most common human birth defects and is generally considered a complex trait. Despite numerous loci identified by genome-wide association studies, the effect sizes of common variants are relatively small, with much of the presumed genetic contribution remaining elusive. We report exome-sequencing results in 209 people from 72 multi-affected families with pedigree structures consistent with autosomal-dominant inheritance and variable penetrance. Herein, pathogenic variants are described in four genes encoding components of the p120-catenin complex (CTNND1, PLEKHA7, PLEKHA5) and an epithelial splicing regulator (ESRP2), in addition to the known CL/P-associated gene, CDH1, which encodes E-cadherin. The findings were also validated in a second cohort of 497 people with NS-CL/P, comprising small families and singletons with pathogenic variants in these genes identified in 14% of multi-affected families and 2% of the replication cohort of smaller families. Enriched expression of each gene/protein in human and mouse embryonic oro-palatal epithelia, demonstration of functional impact of CTNND1 and ESRP2 variants, and recapitulation of the CL/P spectrum in Ctnnd1 knockout mice support a causative role in CL/P pathogenesis. These data show that primary defects in regulators of epithelial cell adhesion are the most significant contributors to NS-CL/P identified to date and that inherited and de novo single gene variants explain a substantial proportion of NS-CL/P.
Keywords: Alleles; Amino Acid Sequence; Animals; Biotinylation; Cadherins; Catenins; Cleft Lip; Cleft Palate; Epithelium; Female; Gene Deletion; Genetic Predisposition to Disease; Humans; Infant; Infant, Newborn; Male; Mice; Mutation; Palate; Pedigree; Syndrome; Whole Exome Sequencing

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability. - Santos-Cortez, Regie Lyn P; Khan, Valeed; Khan, Falak Sher; Mughal, Zaib-Un-Nisa; Chakchouk, Imen; Lee, Kwanghyuk; Rasheed, Memoona; Hamza, Rifat; Acharya, Anushree; Ullah, Ehsan; Saqib, Muhammad Arif Nadeem; Abbe, Izoduwa; et al. (Hum Genet, 2018)
Identification of Mendelian genes for neurodevelopmental disorders using exome sequencing to study autosomal recessive (AR) consanguineous pedigrees has been highly successful. To identify causal variants for syndromic and non-syndromic intellectual disability (ID), exome sequencing was performed using DNA samples from 22 consanguineous Pakistani families with ARID, of which 21 have additional phenotypes including microcephaly. To aid in variant identification, homozygosity mapping and linkage analysis were performed. DNA samples from affected family member(s) from every pedigree underwent exome sequencing. Identified rare damaging exome variants were tested for co-segregation with ID using Sanger sequencing. For seven ARID families, variants were identified in genes not previously associated with ID, including: EI24, FXR1 and TET3 for which knockout mouse models have brain defects; and CACNG7 and TRAPPC10 where cell studies suggest roles in important neural pathways. For two families, the novel ARID genes CARNMT1 and GARNL3 lie within previously reported ID microdeletion regions. We also observed homozygous variants in two ID candidate genes, GRAMD1B and TBRG1, for which each has been previously reported in a single family. An additional 14 families have homozygous variants in established ID genes, of which 11 variants are novel. All ARID genes have increased expression in specific structures of the developing and adult human brain and 91% of the genes are differentially expressed in utero or during early childhood. The identification of novel ARID candidate genes and variants adds to the knowledge base that is required to further understand human brain function and development.
Keywords: Adult; Consanguinity; Family; Female; Genes, Recessive; Genetic Markers; Humans; Intellectual Disability; Male; Middle Aged; Mutation; Neurodevelopmental Disorders; Pedigree

Novel digenic inheritance of PCDH15 and USH1G underlies profound non-syndromic hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Acharya, Anushree; Liaqat, Khurram; Nickerson, Deborah A; Bamshad, Michael J; Shah, Khadim; Ahmad, Wasim; Leal, Suzanne M (BMC Med Genet, 2018)
BACKGROUND: Digenic inheritance is the simplest model of oligenic disease. It can be observed when there is a strong epistatic interaction between two loci. For both syndromic and non-syndromic hearing impairment, several forms of digenic inheritance have been reported. METHODS: We performed exome sequencing in a Pakistani family with profound non-syndromic hereditary hearing impairment to identify the genetic cause of disease. RESULTS: We found that this family displays digenic inheritance for two trans heterozygous missense mutations, one in PCDH15 [p.(Arg1034His)] and another in USH1G [p.(Asp365Asn)]. Both of these genes are known to cause autosomal recessive non-syndromic hearing impairment and Usher syndrome. The protein products of PCDH15 and USH1G function together at the stereocilia tips in the hair cells and are necessary for proper mechanotransduction. Epistasis between Pcdh15 and Ush1G has been previously reported in digenic heterozygous mice. The digenic mice displayed a significant decrease in hearing compared to age-matched heterozygous animals. Until now no human examples have been reported. CONCLUSIONS: The discovery of novel digenic inheritance mechanisms in hereditary hearing impairment will aid in understanding the interaction between defective proteins and further define inner ear function and its interactome.
Keywords: Adult; Animals; Cadherins; Hearing Loss; Heterozygote; Humans; Male; Mechanotransduction, Cellular; Multifactorial Inheritance; Mutation; Nerve Tissue Proteins; Pakistan; Pedigree; Usher Syndromes; Young Adult

A presynaptic congenital myasthenic syndrome attributed to a homozygous sequence variant in LAMA5. - Maselli, Ricardo A; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X; Bamshad, Michael J; Nickerson, Deborah A; Lara, Marian; Ng, Fiona; Lo, Victoria Lee; Pytel, Peter; McDonald, Craig M (Ann N Y Acad Sci, 2018)
We report a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin α5 subunit gene (LAMA5). The variant c.8046C > T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had normal cognitive function, but magnetic resonance brain imaging showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation at 2 Hz showed 50% decrement of compound muscle action potential amplitudes but 250% facilitation immediately after exercise, similar to that seen in Lambert-Eaton myasthenic syndrome. Endplate studies demonstrated a profound reduction of the endplate potential quantal content but normal amplitudes of miniature endplate potentials. Electron microscopy showed endplates with increased postsynaptic folding that were denuded or only partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin α5 to SV2A and impaired laminin-521 cell adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding α-laminins.
Keywords: Adult; Female; Humans; Lambert-Eaton Myasthenic Syndrome; Laminin; Motor Endplate; Myasthenic Syndromes, Congenital; Synaptic Transmission

A variant in LMX1A causes autosomal recessive severe-to-profound hearing impairment. - Schrauwen, Isabelle; Chakchouk, Imen; Liaqat, Khurram; Jan, Abid; Nasir, Abdul; Hussain, Shabir; Nickerson, Deborah A; Bamshad, Michael J; Ullah, Asmat; Ahmad, Wasim; Leal, Suzanne M (Hum Genet, 2018)
Hereditary hearing impairment is a common sensory disorder that is genetically and phenotypically heterogeneous. In this study, we used a homozygosity mapping and exome sequencing strategy to study a consanguineous Pakistani family with autosomal recessive severe-to-profound hearing impairment. This led to the identification of a missense variant (p.Ile369Thr) in the LMX1A gene affecting a conserved residue in the C-terminus of the protein, which was predicted damaging by an in silico bioinformatics analysis. The p.Ile369Thr variant disrupts several C-terminal and homeodomain residue interactions, including an interaction with homeodomain residue p.Val241 that was previously found to be involved in autosomal dominant progressive HI. LIM-homeodomain factor Lmx1a is expressed in the inner ear through development, shows a progressive restriction to non-sensory epithelia, and is important in the separation of the sensory and non-sensory domains in the inner ear. Homozygous Lmx1a mutant mice (Dreher) are deaf with dysmorphic ears with an abnormal morphogenesis and fused and misshapen sensory organs; however, computed tomography performed on a hearing-impaired family member did not reveal any cochleovestibular malformations. Our results suggest that LMX1A is involved in both human autosomal recessive and dominant sensorineural hearing impairment.
Keywords: Adolescent; Adult; Animals; Child; Disease Models, Animal; Ear, Inner; Female; Genes, Dominant; Genes, Recessive; Hearing Loss; Hearing Loss, Sensorineural; Homozygote; Humans; LIM-Homeodomain Proteins; Male; Mice; Mutation, Missense; Pedigree; Transcription Factors; Whole Exome Sequencing

Activation of a cryptic splice site in the mitochondrial elongation factor GFM1 causes combined OXPHOS deficiency. - Simon, Mariella T; Ng, Bobby G; Friederich, Marisa W; Wang, Raymond Y; Boyer, Monica; Kircher, Martin; Collard, Renata; Buckingham, Kati J; Chang, Richard; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; et al. (Mitochondrion, 2017)
We report the clinical, biochemical, and molecular findings in two brothers with encephalopathy and multi-systemic disease. Abnormal transferrin glycoforms were suggestive of a type I congenital disorder of glycosylation (CDG). While exome sequencing was negative for CDG related candidate genes, the testing revealed compound heterozygous mutations in the mitochondrial elongation factor G gene (GFM1). One of the mutations had been reported previously while the second, novel variant was found deep in intron 6, activating a cryptic splice site. Functional studies demonstrated decreased GFM1 protein levels, suggested disrupted assembly of mitochondrial complexes III and V and decreased activities of mitochondrial complexes I and IV, all indicating combined OXPHOS deficiency.
Keywords: Child; Child, Preschool; Congenital Abnormalities; Gene Expression; Humans; Infant; Infant, Newborn; Male; Mitochondrial Proteins; Oxidative Phosphorylation; Peptide Elongation Factor G; RNA Splice Sites

DUOX2 Gene Mutation Manifesting as Resistance to Thyrotropin Phenotype. - Srichomkwun, Panudda; Takamatsu, Junta; Nickerson, Deborah A; Bamshad, Michael J; Chong, Jessica X; Refetoff, Samuel (Thyroid, 2017)
Resistance to thyrotropin (TSH) (RTSH; defined by elevated TSH and a normal or hypoplastic thyroid gland) can be caused by mutations in genes encoding the TSH receptor and PAX8, and it has been linked to a locus on chromosome 15. In two nonconsanguineous families with nongoitrous euthyroid hyperthyrotropinemia, typical of the RTSH phenotype, exome analysis identified five rare DUOX2 gene variants (p.A649E, p.P1391A, p.R885L, p.G488R, and p.SF965-6SfsX29) found to be pathogenic. This form of nongoitrous dyshormonogenesis masquerades both clinically and biochemically as RTSH. Accordingly, mutations in DUOX2 should be added to those of SLC26A4 as causes of RTSH.
Keywords: Child, Preschool; Congenital Hypothyroidism; Dual Oxidases; Female; Genotype; Humans; Male; Mutation; Pedigree; Phenotype; Thyroid Hormone Resistance Syndrome; Thyrotropin

Encephalopathy caused by novel mutations in the CMP-sialic acid transporter, SLC35A1. - Ng, Bobby G; Asteggiano, Carla G; Kircher, Martin; Buckingham, Kati J; Raymond, Kimiyo; Nickerson, Deborah A; Shendure, Jay; Bamshad, Michael J; Ensslen, Matthias; Freeze, Hudson H (Am J Med Genet A, 2017)
Transport of activated nucleotide-sugars into the Golgi is critical for proper glycosylation and mutations in these transporters cause a group of rare genetic disorders termed congenital disorders of glycosylation. We performed exome sequencing on an individual with a profound neurological presentation and identified rare compound heterozygous mutations, p.Thr156Arg and p.Glu196Lys, in the CMP-sialic acid transporter, SLC35A1. Patient primary fibroblasts and serum showed a considerable decrease in the amount of N- and O-glycans terminating in sialic acid. Direct measurement of CMP-sialic acid transport into the Golgi showed a substantial decrease in overall rate of transport. Here we report the identification of the third patient with CMP-sialic acid transporter deficiency, who presented with severe neurological phenotype, but without hematological abnormalities.
Keywords: Animals; Brain Diseases; Child; CHO Cells; Cricetinae; Cricetulus; Female; Flow Cytometry; Golgi Apparatus; Humans; Mutation; N-Acetylneuraminic Acid; Nucleotide Transport Proteins; Whole Exome Sequencing

Identification of ASAH1 as a susceptibility gene for familial keloids. - Santos-Cortez, Regie Lyn P; Hu, Ying; Sun, Fanyue; Benahmed-Miniuk, Fairouz; Tao, Jian; Kanaujiya, Jitendra K; Ademola, Samuel; Fadiora, Solomon; Odesina, Victoria; Nickerson, Deborah A; Bamshad, Michael J; Olaitan, Peter B; et al. (Eur J Hum Genet, 2017)
Keloids result from abnormal proliferative scar formation with scar tissue expanding beyond the margin of the original wound and are mostly found in individuals of sub-Saharan African descent. The etiology of keloids has not been resolved but previous studies suggest that keloids are a genetically heterogeneous disorder. Although possible candidate genes have been suggested by genome-wide association studies using common variants, by upregulation in keloids or their involvement in syndromes that include keloid formation, rare coding variants that contribute to susceptibility in non-syndromic keloid formation have not been previously identified. Through analysis of whole-genome data we mapped a locus to chromosome 8p23.3-p21.3 with a statistically significant maximum multipoint LOD score of 4.48. This finding was followed up using exome sequencing and led to the identification of a c.1202T>C (p.(Leu401Pro)) variant in the N-acylsphingosine amidohydrolase (ASAH1) gene that co-segregates with the keloid phenotype in a large Yoruba family. ASAH1 is an acid ceramidase known to be involved in tumor formation by controlling the ratio of ceramide and sphingosine. ASAH1 is also involved in cell proliferation and inflammation, and may affect the development of keloids via multiple mechanisms. Functional studies need to clarify the role of the ASAH1 variant in wound healing.
Keywords: Acid Ceramidase; Adult; Female; Humans; Keloid; Male; Mutation, Missense; Pedigree

International Cooperation to Enable the Diagnosis of All Rare Genetic Diseases. - Boycott, Kym M; Rath, Ana; Chong, Jessica X; Hartley, Taila; Alkuraya, Fowzan S; Baynam, Gareth; Brookes, Anthony J; Brudno, Michael; Carracedo, Angel; den Dunnen, Johan T; Dyke, Stephanie O M; Estivill, Xavier; et al. (Am J Hum Genet, 2017)
Provision of a molecularly confirmed diagnosis in a timely manner for children and adults with rare genetic diseases shortens their "diagnostic odyssey," improves disease management, and fosters genetic counseling with respect to recurrence risks while assuring reproductive choices. In a general clinical genetics setting, the current diagnostic rate is approximately 50%, but for those who do not receive a molecular diagnosis after the initial genetics evaluation, that rate is much lower. Diagnostic success for these more challenging affected individuals depends to a large extent on progress in the discovery of genes associated with, and mechanisms underlying, rare diseases. Thus, continued research is required for moving toward a more complete catalog of disease-related genes and variants. The International Rare Diseases Research Consortium (IRDiRC) was established in 2011 to bring together researchers and organizations invested in rare disease research to develop a means of achieving molecular diagnosis for all rare diseases. Here, we review the current and future bottlenecks to gene discovery and suggest strategies for enabling progress in this regard. Each successful discovery will define potential diagnostic, preventive, and therapeutic opportunities for the corresponding rare disease, enabling precision medicine for this patient population.
Keywords: Databases, Factual; Exome; Genome, Human; Humans; International Cooperation; Rare Diseases

Loss-of-Function Mutations in YY1AP1 Lead to Grange Syndrome and a Fibromuscular Dysplasia-Like Vascular Disease. - Guo, Dong-Chuan; Duan, Xue-Yan; Regalado, Ellen S; Mellor-Crummey, Lauren; Kwartler, Callie S; Kim, Dong; Lieberman, Kenneth; de Vries, Bert B A; Pfundt, Rolph; Schinzel, Albert; Kotzot, Dieter; Shen, Xuetong; et al. (Am J Hum Genet, 2017)
Fibromuscular dysplasia (FMD) is a heterogeneous group of non-atherosclerotic and non-inflammatory arterial diseases that primarily involves the renal and cerebrovascular arteries. Grange syndrome is an autosomal-recessive condition characterized by severe and early-onset vascular disease similar to FMD and variable penetrance of brachydactyly, syndactyly, bone fragility, and learning disabilities. Exome-sequencing analysis of DNA from three affected siblings with Grange syndrome identified compound heterozygous nonsense variants in YY1AP1, and homozygous nonsense or frameshift YY1AP1 variants were subsequently identified in additional unrelated probands with Grange syndrome. YY1AP1 encodes yin yang 1 (YY1)-associated protein 1 and is an activator of the YY1 transcription factor. We determined that YY1AP1 localizes to the nucleus and is a component of the INO80 chromatin remodeling complex, which is responsible for transcriptional regulation, DNA repair, and replication. Molecular studies revealed that loss of YY1AP1 in vascular smooth muscle cells leads to cell cycle arrest with decreased proliferation and increased levels of the cell cycle regulator p21/WAF/CDKN1A and disrupts TGF-β-driven differentiation of smooth muscle cells. Identification of YY1AP1 mutations as a cause of FMD indicates that this condition can result from underlying genetic variants that significantly alter the phenotype of vascular smooth muscle cells.
Keywords: Adolescent; Adult; Bone and Bones; Brachydactyly; Cell Cycle Checkpoints; Exome; Female; Fibromuscular Dysplasia; Genes, Recessive; Heterozygote; Homozygote; Humans; Learning Disorders; Male; Middle Aged; Muscle, Smooth, Vascular; Mutation; Nuclear Proteins; Pedigree; Syndactyly; Syndrome; Transcription Factors

MED resulting from recessively inherited mutations in the gene encoding calcium-activated nucleotidase CANT1. - Balasubramanian, Karthika; Li, Bing; Krakow, Deborah; Nevarez, Lisette; Ho, Patric J; Ainsworth, Julia A; Nickerson, Deborah A; Bamshad, Michael J; Immken, LaDonna; Lachman, Ralph S; Cohn, Daniel H (Am J Med Genet A, 2017)
Multiple Epiphyseal Dysplasia (MED) is a relatively mild skeletal dysplasia characterized by mild short stature, joint pain, and early-onset osteoarthropathy. Dominantly inherited mutations in COMP, MATN3, COL9A1, COL9A2, and COL9A3, and recessively inherited mutations in SLC26A2, account for the molecular basis of disease in about 80-85% of the cases. In two families with recurrent MED of an unknown molecular basis, we used exome sequencing and candidate gene analysis to identify homozygosity for recessively inherited missense mutations in CANT1, which encodes calcium-activated nucleotidase 1. The MED phenotype is thus allelic to the more severe Desbuquois dysplasia phenotype and the results identify CANT1 as a second locus for recessively inherited MED.
Keywords: Adult; Base Sequence; Child; Child, Preschool; Exome; Female; Genes, Recessive; Humans; Male; Mutation, Missense; Nucleotidases; Osteochondrodysplasias; Pedigree; Radiography

Mutations in ARMC9, which Encodes a Basal Body Protein, Cause Joubert Syndrome in Humans and Ciliopathy Phenotypes in Zebrafish. - Van De Weghe, Julie C; Rusterholz, Tamara D S; Latour, Brooke; Grout, Megan E; Aldinger, Kimberly A; Shaheen, Ranad; Dempsey, Jennifer C; Maddirevula, Sateesh; Cheng, Yong-Han H; Phelps, Ian G; Gesemann, Matthias; Goel, Himanshu; et al. (Am J Hum Genet, 2017)
Joubert syndrome (JS) is a recessive neurodevelopmental disorder characterized by hypotonia, ataxia, abnormal eye movements, and variable cognitive impairment. It is defined by a distinctive brain malformation known as the "molar tooth sign" on axial MRI. Subsets of affected individuals have malformations such as coloboma, polydactyly, and encephalocele, as well as progressive retinal dystrophy, fibrocystic kidney disease, and liver fibrosis. More than 35 genes have been associated with JS, but in a subset of families the genetic cause remains unknown. All of the gene products localize in and around the primary cilium, making JS a canonical ciliopathy. Ciliopathies are unified by their overlapping clinical features and underlying mechanisms involving ciliary dysfunction. In this work, we identify biallelic rare, predicted-deleterious ARMC9 variants (stop-gain, missense, splice-site, and single-exon deletion) in 11 individuals with JS from 8 families, accounting for approximately 1% of the disorder. The associated phenotypes range from isolated neurological involvement to JS with retinal dystrophy, additional brain abnormalities (e.g., heterotopia, Dandy-Walker malformation), pituitary insufficiency, and/or synpolydactyly. We show that ARMC9 localizes to the basal body of the cilium and is upregulated during ciliogenesis. Typical ciliopathy phenotypes (curved body shape, retinal dystrophy, coloboma, and decreased cilia) in a CRISPR/Cas9-engineered zebrafish mutant model provide additional support for ARMC9 as a ciliopathy-associated gene. Identifying ARMC9 mutations as a cause of JS takes us one step closer to a full genetic understanding of this important disorder and enables future functional work to define the central biological mechanisms underlying JS and other ciliopathies.
Keywords: Abnormalities, Multiple; Animals; Armadillo Domain Proteins; Basal Bodies; Base Sequence; Brain; Cerebellum; Cilia; Ciliopathies; Diagnostic Imaging; Exome; Eye Abnormalities; Genetic Predisposition to Disease; Humans; Kidney Diseases, Cystic; Mutation; Phenotype; Retina; Sequence Analysis, DNA; Up-Regulation; Zebrafish; Zebrafish Proteins

My46: a Web-based tool for self-guided management of genomic test results in research and clinical settings. - Tabor, Holly K; Jamal, Seema M; Yu, Joon-Ho; Crouch, Julia M; Shankar, Aditi G; Dent, Karin M; Anderson, Nick; Miller, Damon A; Futral, Brett T; Bamshad, Michael J (Genet Med, 2017)
A major challenge to implementing precision medicine is the need for an efficient and cost-effective strategy for returning individual genomic test results that is easily scalable and can be incorporated into multiple models of clinical practice. My46 is a Web-based tool for managing the return of genetic results that was designed and developed to support a wide range of approaches to disclosing results, ranging from traditional face-to-face disclosure to self-guided models. My46 has five key functions: set and modify results-return preferences, return results, educate, manage the return of results, and assess the return of results. These key functions are supported by six distinct modules and a suite of features that enhance the user experience, ease site navigation, facilitate knowledge sharing, and enable results-return tracking. My46 is a potentially effective solution for returning results and supports current trends toward shared decision making between patients and providers and patient-driven health management.Genet Med 19 4, 467-475.
Keywords: Biomedical Research; Computational Biology; Decision Making; Genomics; Humans; Internet; Medical Informatics; Patient Access to Records; Precision Medicine

Presynaptic congenital myasthenic syndrome with a homozygous sequence variant in LAMA5 combines myopia, facial tics, and failure of neuromuscular transmission. - Maselli, Ricardo A; Arredondo, Juan; Vázquez, Jessica; Chong, Jessica X; Bamshad, Michael J; Nickerson, Deborah A; Lara, Marian; Ng, Fiona; Lo, Victoria L; Pytel, Peter; McDonald, Craig M (Am J Med Genet A, 2017)
Defects in genes encoding the isoforms of the laminin alpha subunit have been linked to various phenotypic manifestations, including brain malformations, muscular dystrophy, ocular defects, cardiomyopathy, and skin abnormalities. We report here a severe defect of neuromuscular transmission in a consanguineous patient with a homozygous variant in the laminin alpha-5 subunit gene (LAMA5). The variant c.8046C>T (p.Arg2659Trp) is rare and has a predicted deleterious effect. The affected individual, who also carries a rare homozygous sequence variant in LAMA1, had muscle weakness, myopia, and facial tics. Magnetic resonance imaging of brain showed mild volume loss and periventricular T2 prolongation. Repetitive nerve stimulation revealed 50% decrement of compound muscle action potential amplitudes and 250% facilitation immediately after exercise, Endplate studies identified a profound reduction of the endplate potential quantal content and endplates with normal postsynaptic folding that were denuded or partially occupied by small nerve terminals. Expression studies revealed that p.Arg2659Trp caused decreased binding of laminin alpha-5 to SV2A and impaired laminin-521 cell-adhesion and cell projection support in primary neuronal cultures. In summary, this report describing severe neuromuscular transmission failure in a patient with a LAMA5 mutation expands the list of phenotypes associated with defects in genes encoding alpha-laminins.
Keywords: Adult; Face; Female; Homozygote; Humans; Laminin; Myasthenic Syndromes, Congenital; Myopia; Neuromuscular Junction Diseases; Tics; Young Adult

Sequence variants in nine different genes underlying rare skin disorders in 10 consanguineous families. - Shah, Khadim; Mehmood, Sabba; Jan, Abid; Abbe, Izoduwa; Hussain Ali, Raja; Khan, Anwar; Chishti, Muhammad S; Lee, Kwanghyuk; Ahmad, Farooq; Ansar, Muhammad; Shahzad, Shaheen; Nickerson, Deborah A; et al. (Int J Dermatol, 2017)
BACKGROUND: Genodermatoses represent genetic anomalies of skin tissues including hair follicles, sebaceous glands, eccrine glands, nails, and teeth. Ten consanguineous families segregating various genodermatosis phenotypes were investigated in the present study. METHODS: Homozygosity mapping, exome, and Sanger sequencing were employed to search for the disease-causing variants in the 10 families. RESULTS: Exome sequencing identified seven homozygous sequence variants in different families, including: c.27delT in FERMT1; c.836delA in ABHD5; c.2453C>T in ERCC5; c.5314C>T in COL7A1; c.1630C>T in ALOXE3; c.502C>T in PPOX; and c.10G>T in ALDH3A2. Sanger sequencing revealed three homozygous variants: c.1718 + 2A>G in FERMT1; c.10459A>T in FLG; and c.92delT in the KRT14 genes as the underlying genetic cause of skin phenotypes. CONCLUSION: This study supports the use of exome sequencing as a powerful, efficient tool for identifying genes that underlie rare monogenic skin disorders.
Keywords: 1-Acylglycerol-3-Phosphate O-Acyltransferase; Aldehyde Oxidoreductases; Blister; Collagen Type VII; Consanguinity; DNA Mutational Analysis; DNA-Binding Proteins; Endonucleases; Epidermolysis Bullosa; Epidermolysis Bullosa Dystrophica; Epidermolysis Bullosa Simplex; Exome; Female; Flavoproteins; Homozygote; Humans; Ichthyosiform Erythroderma, Congenital; Ichthyosis Vulgaris; Ichthyosis, Lamellar; INDEL Mutation; Intermediate Filament Proteins; Keratin-14; Lipid Metabolism, Inborn Errors; Lipoxygenase; Male; Membrane Proteins; Mitochondrial Proteins; Muscular Diseases; Neoplasm Proteins; Nuclear Proteins; Pedigree; Periodontal Diseases; Phenotype; Photosensitivity Disorders; Porphyria, Variegate; Protoporphyrinogen Oxidase; Rare Diseases; Sjogren-Larsson Syndrome; Skin Diseases, Genetic; Transcription Factors; Xeroderma Pigmentosum

Sequencing of sporadic Attention-Deficit Hyperactivity Disorder (ADHD) identifies novel and potentially pathogenic de novo variants and excludes overlap with genes associated with autism spectrum disorder. - Kim, Daniel Seung; Burt, Amber A; Ranchalis, Jane E; Wilmot, Beth; Smith, Joshua D; Patterson, Karynne E; Coe, Bradley P; Li, Yatong K; Bamshad, Michael J; Nikolas, Molly; Eichler, Evan E; Swanson, James M; et al. (Am J Med Genet B Neuropsychiatr Genet, 2017)
Attention-Deficit Hyperactivity Disorder (ADHD) has high heritability; however, studies of common variation account for <5% of ADHD variance. Using data from affected participants without a family history of ADHD, we sought to identify de novo variants that could account for sporadic ADHD. Considering a total of 128 families, two analyses were conducted in parallel: first, in 11 unaffected parent/affected proband trios (or quads with the addition of an unaffected sibling) we completed exome sequencing. Six de novo missense variants at highly conserved bases were identified and validated from four of the 11 families: the brain-expressed genes TBC1D9, DAGLA, QARS, CSMD2, TRPM2, and WDR83. Separately, in 117 unrelated probands with sporadic ADHD, we sequenced a panel of 26 genes implicated in intellectual disability (ID) and autism spectrum disorder (ASD) to evaluate whether variation in ASD/ID-associated genes were also present in participants with ADHD. Only one putative deleterious variant (Gln600STOP) in CHD1L was identified; this was found in a single proband. Notably, no other nonsense, splice, frameshift, or highly conserved missense variants in the 26 gene panel were identified and validated. These data suggest that de novo variant analysis in families with independently adjudicated sporadic ADHD diagnosis can identify novel genes implicated in ADHD pathogenesis. Moreover, that only one of the 128 cases (0.8%, 11 exome, and 117 MIP sequenced participants) had putative deleterious variants within our data in 26 genes related to ID and ASD suggests significant independence in the genetic pathogenesis of ADHD as compared to ASD and ID phenotypes. © 2017 Wiley Periodicals, Inc.
Keywords: Adult; Attention Deficit Disorder with Hyperactivity; Autism Spectrum Disorder; Biomarkers; Child; Exome; Female; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Mutation, Missense; Phenotype

Survival beyond the perinatal period expands the phenotypes caused by mutations in GLE1. - Said, Edith; Chong, Jessica X; Hempel, Maja; Denecke, Jonas; Soler, Paul; Strom, Tim; Nickerson, Deborah A; Kubisch, Christian; Bamshad, Michael J; Lessel, Davor (Am J Med Genet A, 2017)
Mutations in GLE1 underlie Lethal Congenital Contracture syndrome (LCCS) and Lethal Arthrogryposis with Anterior Horn Cell Disease (LAAHD). Both LCCS and LAAHD are characterized by reduced fetal movements, congenital contractures, and a severe form of motor neuron disease that results in fetal death or death in the perinatal period, respectively. We identified bi-allelic mutations in GLE1 in two unrelated individuals with motor delays, feeding difficulties, and respiratory insufficiency who survived beyond the perinatal period. Each affected child had missense variants predicted to result in amino acid substitutions near the C-terminus of GLE1 that are predicted to disrupt protein-protein interaction or GLE1 protein targeting. We hypothesize that mutations that preserve function of the coiled-coil domain of GLE1 cause LAAHD whereas mutations that abolish the function of the coiled-coil domain cause LCCS. The phenotype of LAAHD is now expanded to include multiple individuals surviving into childhood suggesting that LAAHD is a misnomer and should be re-named Arthrogryposis with Anterior Horn Cell Disease (AAHD).
Keywords: Arthrogryposis; Child, Preschool; Female; Genetic Predisposition to Disease; Humans; Male; Motor Disorders; Motor Neuron Disease; Mutation; Nucleocytoplasmic Transport Proteins; Pedigree; Pregnancy

ALG1-CDG: Clinical and Molecular Characterization of 39 Unreported Patients. - Ng, Bobby G; Shiryaev, Sergey A; Rymen, Daisy; Eklund, Erik A; Raymond, Kimiyo; Kircher, Martin; Abdenur, Jose E; Alehan, Fusun; Midro, Alina T; Bamshad, Michael J; Barone, Rita; Berry, Gerard T; et al. (Hum Mutat, 2016)
Congenital disorders of glycosylation (CDG) arise from pathogenic mutations in over 100 genes leading to impaired protein or lipid glycosylation. ALG1 encodes a β1,4 mannosyltransferase that catalyzes the addition of the first of nine mannose moieties to form a dolichol-lipid linked oligosaccharide intermediate required for proper N-linked glycosylation. ALG1 mutations cause a rare autosomal recessive disorder termed ALG1-CDG. To date 13 mutations in 18 patients from 14 families have been described with varying degrees of clinical severity. We identified and characterized 39 previously unreported cases of ALG1-CDG from 32 families and add 26 new mutations. Pathogenicity of each mutation was confirmed based on its inability to rescue impaired growth or hypoglycosylation of a standard biomarker in an alg1-deficient yeast strain. Using this approach we could not establish a rank order comparison of biomarker glycosylation and patient phenotype, but we identified mutations with a lethal outcome in the first two years of life. The recently identified protein-linked xeno-tetrasaccharide biomarker, NeuAc-Gal-GlcNAc2 , was seen in all 27 patients tested. Our study triples the number of known patients and expands the molecular and clinical correlates of this disorder.
Keywords: Biomarkers; Congenital Disorders of Glycosylation; Female; Genes, Lethal; Glycosylation; Humans; Male; Mannosyltransferases; Mutation; Polysaccharides; Sequence Analysis, DNA; Survival Analysis

Autosomal-Recessive Hearing Impairment Due to Rare Missense Variants within S1PR2. - Santos-Cortez, Regie Lyn P; Faridi, Rabia; Rehman, Atteeq U; Lee, Kwanghyuk; Ansar, Muhammad; Wang, Xin; Morell, Robert J; Isaacson, Rivka; Belyantseva, Inna A; Dai, Hang; Acharya, Anushree; Qaiser, Tanveer A; et al. (Am J Hum Genet, 2016)
The sphingosine-1-phosphate receptors (S1PRs) are a well-studied class of transmembrane G protein-coupled sphingolipid receptors that mediate multiple cellular processes. However, S1PRs have not been previously reported to be involved in the genetic etiology of human traits. S1PR2 lies within the autosomal-recessive nonsyndromic hearing impairment (ARNSHI) locus DFNB68 on 19p13.2. From exome sequence data we identified two pathogenic S1PR2 variants, c.323G>C (p.Arg108Pro) and c.419A>G (p.Tyr140Cys). Each of these variants co-segregates with congenital profound hearing impairment in consanguineous Pakistani families with maximum LOD scores of 6.4 for family DEM4154 and 3.3 for family PKDF1400. Neither S1PR2 missense variant was reported among ∼120,000 chromosomes in the Exome Aggregation Consortium database, in 76 unrelated Pakistani exomes, or in 720 Pakistani control chromosomes. Both DNA variants affect highly conserved residues of S1PR2 and are predicted to be damaging by multiple bioinformatics tools. Molecular modeling predicts that these variants affect binding of sphingosine-1-phosphate (p.Arg108Pro) and G protein docking (p.Tyr140Cys). In the previously reported S1pr2(-/-) mice, stria vascularis abnormalities, organ of Corti degeneration, and profound hearing loss were observed. Additionally, hair cell defects were seen in both knockout mice and morphant zebrafish. Family PKDF1400 presents with ARNSHI, which is consistent with the lack of gross malformations in S1pr2(-/-) mice, whereas family DEM4154 has lower limb malformations in addition to hearing loss. Our findings suggest the possibility of developing therapies against hair cell damage (e.g., from ototoxic drugs) through targeted stimulation of S1PR2.
Keywords: Amino Acid Sequence; Asian Continental Ancestry Group; Chromosomes, Human, Pair 19; Exome; Genes, Recessive; Hearing Loss; Humans; Lod Score; Logistic Models; Lysophospholipids; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Pedigree; Phenotype; Receptors, Lysosphingolipid; Sphingosine

Expansion of the spectrum of ITGB6-related disorders to adolescent alopecia, dentogingival abnormalities and intellectual disability. - Ansar, Muhammad; Jan, Abid; Santos-Cortez, Regie Lyn P; Wang, Xin; Suliman, Muhammad; Acharya, Anushree; Habib, Rabia; Abbe, Izoduwa; Ali, Ghazanfar; Lee, Kwanghyuk; Smith, Joshua D; Nickerson, Deborah A; et al. (Eur J Hum Genet, 2016)
Alopecia with mental retardation (APMR) is a very rare disorder. In this study, we report on a consanguineous Pakistani family (AP91) with mild-to-moderate intellectual disability, adolescent alopecia and dentogingival abnormalities. Using homozygosity mapping, linkage analysis and exome sequencing, we identified a novel rare missense variant c.898G>A (p.(Glu300Lys)) in ITGB6, which co-segregates with the phenotype within the family and is predicted to be deleterious. Structural modeling shows that Glu300 lies in the β-propeller domain, and is surrounded by several residues that are important for heterodimerization with α integrin. Previous studies showed that ITGB6 variants can cause amelogenesis imperfecta in humans, but patients from family AP91 who are homozygous for the c.898G>A variant present with neurological and dermatological features, indicating a role for ITGB6 beyond enamel formation. Our study demonstrates that a rare deleterious variant within ITGB6 causes not only dentogingival anomalies but also intellectual disability and alopecia.
Keywords: Adolescent; Adult; Alopecia; Child; Female; Humans; Integrin beta Chains; Intellectual Disability; Male; Mutation, Missense; Pedigree; Phenotype; Protein Domains; Syndrome; Tooth Abnormalities

FOXE3 mutations predispose to thoracic aortic aneurysms and dissections. - Kuang, Shao-Qing; Medina-Martinez, Olga; Guo, Dong-Chuan; Gong, Limin; Regalado, Ellen S; Reynolds, Corey L; Boileau, Catherine; Jondeau, Guillaume; Prakash, Siddharth K; Kwartler, Callie S; Zhu, Lawrence Yang; Peters, Andrew M; et al. (J Clin Invest, 2016)
The ascending thoracic aorta is designed to withstand biomechanical forces from pulsatile blood. Thoracic aortic aneurysms and acute aortic dissections (TAADs) occur as a result of genetically triggered defects in aortic structure and a dysfunctional response to these forces. Here, we describe mutations in the forkhead transcription factor FOXE3 that predispose mutation-bearing individuals to TAAD. We performed exome sequencing of a large family with multiple members with TAADs and identified a rare variant in FOXE3 with an altered amino acid in the DNA-binding domain (p.Asp153His) that segregated with disease in this family. Additional pathogenic FOXE3 variants were identified in unrelated TAAD families. In mice, Foxe3 deficiency reduced smooth muscle cell (SMC) density and impaired SMC differentiation in the ascending aorta. Foxe3 expression was induced in aortic SMCs after transverse aortic constriction, and Foxe3 deficiency increased SMC apoptosis and ascending aortic rupture with increased aortic pressure. These phenotypes were rescued by inhibiting p53 activity, either by administration of a p53 inhibitor (pifithrin-α), or by crossing Foxe3-/- mice with p53-/- mice. Our data demonstrate that FOXE3 mutations lead to a reduced number of aortic SMCs during development and increased SMC apoptosis in the ascending aorta in response to increased biomechanical forces, thus defining an additional molecular pathway that leads to familial thoracic aortic disease.
Keywords: Adult; Aneurysm, Dissecting; Animals; Aorta; Aortic Aneurysm, Thoracic; Apoptosis; Cells, Cultured; Cyclin-Dependent Kinase Inhibitor p21; Female; Forkhead Transcription Factors; Gene Expression; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Muscle, Smooth, Vascular; Mutation, Missense; Myocytes, Smooth Muscle; Pedigree; Tumor Suppressor Protein p53; Vascular Remodeling; Zebrafish

Gene discovery for Mendelian conditions via social networking: de novo variants in KDM1A cause developmental delay and distinctive facial features. - Chong, Jessica X; Yu, Joon-Ho; Lorentzen, Peter; Park, Karen M; Jamal, Seema M; Tabor, Holly K; Rauch, Anita; Saenz, Margarita Sifuentes; Boltshauser, Eugen; Patterson, Karynne E; Nickerson, Deborah A; Bamshad, Michael J (Genet Med, 2016)
PURPOSE: The pace of Mendelian gene discovery is slowed by the "n-of-1 problem"-the difficulty of establishing the causality of a putatively pathogenic variant in a single person or family. Identification of an unrelated person with an overlapping phenotype and suspected pathogenic variant in the same gene can overcome this barrier, but it is often impeded by lack of a convenient or widely available way to share data on candidate variants/genes among families, clinicians, and researchers. METHODS: Social networking among families, clinicians, and researchers was used to identify three children with variants of unknown significance in KDM1A and similar phenotypes. RESULTS: De novo variants in KDM1A underlie a new syndrome characterized by developmental delay and distinctive facial features. CONCLUSION: Social networking is a potentially powerful strategy to discover genes for rare Mendelian conditions, particularly those with nonspecific phenotypic features. To facilitate the efforts of families to share phenotypic and genomic information with each other, clinicians, and researchers, we developed the Repository for Mendelian Genomics Family Portal (RMD-FP; http://uwcmg.org/#/family). Design and development of MyGene2 (http://www.mygene2.org), a Web-based tool that enables families, clinicians, and researchers to search for gene matches based on analysis of phenotype and exome data deposited into the RMD-FP, is under way.Genet Med 18 8, 788-795.
Keywords: Child; Child, Preschool; Databases, Factual; Developmental Disabilities; Female; Genetic Association Studies; Histone Demethylases; Humans; Information Dissemination; Male; Mutation, Missense; Phenotype; Social Networking; Web Browser

LOX Mutations Predispose to Thoracic Aortic Aneurysms and Dissections. - Guo, Dong-Chuan; Regalado, Ellen S; Gong, Limin; Duan, Xueyan; Santos-Cortez, Regie Lyn P; Arnaud, Pauline; Ren, Zhao; Cai, Bo; Hostetler, Ellen M; Moran, Rocio; Liang, David; Estrera, Anthony; et al. (Circ Res, 2016)
RATIONALE: Mutations in several genes have been identified that are responsible for 25% of families with familial thoracic aortic aneurysms and dissections. However, the causative gene remains unknown in 75% of families. OBJECTIVES: To identify the causative mutation in families with autosomal dominant inheritance of thoracic aortic aneurysms and dissections. METHODS AND RESULTS: Exome sequencing was used to identify the mutation responsible for a large family with thoracic aortic aneurysms and dissections. A heterozygous rare variant, c.839G>T (p.Ser280Arg), was identified in LOX, encoding a lysyl oxidase, that segregated with disease in the family. Sanger and exome sequencing was used to investigate mutations in LOX in an additional 410 probands from unrelated families. Additional LOX rare variants that segregated with disease in families were identified, including c.125G>A (p.Trp42*), c.604G>T (p.Gly202*), c.743C>T (p.Thr248Ile), c.800A>C (p.Gln267Pro), and c.1044T>A (p.Ser348Arg). The altered amino acids cause haploinsufficiency for LOX or are located at a highly conserved LOX catalytic domain, which is relatively invariant in the population. Expression of the LOX variants p.Ser280Arg and p.Ser348Arg resulted in significantly lower lysyl oxidase activity when compared with the wild-type protein. Individuals with LOX variants had fusiform enlargement of the root and ascending thoracic aorta, leading to ascending aortic dissections. CONCLUSIONS: These data, along with previous studies showing that the deficiency of LOX in mice or inhibition of lysyl oxidases in turkeys and rats causes aortic dissections, support the conclusion that rare genetic variants in LOX predispose to thoracic aortic disease.
Keywords: Adult; Aged; Amino Acid Sequence; Aneurysm, Dissecting; Aortic Aneurysm, Thoracic; Female; Genetic Variation; Humans; Male; Middle Aged; Molecular Sequence Data; Mutation; Pedigree; Protein-Lysine 6-Oxidase

Mitral regurgitation as a phenotypic manifestation of nonphotosensitive trichothiodystrophy due to a splice variant in MPLKIP. - Shah, Khadim; Ali, Raja Hussain; Ansar, Muhammad; Lee, Kwanghyuk; Chishti, Muhammad Salman; Abbe, Izoduwa; Li, Biao; Smith, Joshua D; Nickerson, Deborah A; Shendure, Jay; Coucke, Paul J; Steyaert, Wouter; et al. (BMC Med Genet, 2016)
BACKGROUND: Nonphotosensitive trichothiodystrophy (TTDN) is a rare autosomal recessive disorder of neuroectodermal origin. The condition is marked by hair abnormalities, intellectual impairment, nail dystrophies and susceptibility to infections but with no UV sensitivity. METHODS: We identified three consanguineous Pakistani families with varied TTDN features and used homozygosity mapping, linkage analysis, and Sanger and exome sequencing in order to identify pathogenic variants. Haplotype analysis was performed and haplotype age estimated. A splicing assay was used to validate the effect of the MPLKIP splice variant on expression. RESULTS: Affected individuals from all families exhibit several TTDN features along with a heart-specific feature, i.e. mitral regurgitation. Exome sequencing in the probands from families ED168 and ED241 identified a homozygous splice mutation c.339 + 1G > A within MPLKIP. The same splice variant co-segregates with TTDN in a third family ED210. The MPLKIP splice variant was not found in public databases, e.g. the Exome Aggregation Consortium, and in unrelated Pakistani controls. Functional analysis of the splice variant confirmed intron retention, which leads to protein truncation and loss of a phosphorylation site. Haplotype analysis identified a 585.1-kb haplotype which includes the MPLKIP variant, supporting the existence of a founder haplotype that is estimated to be 25,900 years old. CONCLUSION: This study extends the allelic and phenotypic spectra of MPLKIP-related TTDN, to include a splice variant that causes cardiomyopathy as part of the TTDN phenotype.
Keywords: Adaptor Proteins, Signal Transducing; Adolescent; Adult; Alleles; Asian Continental Ancestry Group; Child; Cloning, Molecular; Exome; Female; Genetic Linkage; Haplotypes; HEK293 Cells; Homozygote; Humans; Introns; Male; Mitral Valve Insufficiency; Pakistan; Pedigree; Phenotype; Polymorphism, Single Nucleotide; RNA Splicing; Sequence Analysis, DNA; Trichothiodystrophy Syndromes; Young Adult

Recessive Inactivating Mutations in TBCK, Encoding a Rab GTPase-Activating Protein, Cause Severe Infantile Syndromic Encephalopathy. - Chong, Jessica X; Caputo, Viviana; Phelps, Ian G; Stella, Lorenzo; Worgan, Lisa; Dempsey, Jennifer C; Nguyen, Alina; Leuzzi, Vincenzo; Webster, Richard; Pizzuti, Antonio; Marvin, Colby T; Ishak, Gisele E; et al. (Am J Hum Genet, 2016)
Infantile encephalopathies are a group of clinically and biologically heterogeneous disorders for which the genetic basis remains largely unknown. Here, we report a syndromic neonatal encephalopathy characterized by profound developmental disability, severe hypotonia, seizures, diminished respiratory drive requiring mechanical ventilation, brain atrophy, dysgenesis of the corpus callosum, cerebellar vermis hypoplasia, and facial dysmorphism. Biallelic inactivating mutations in TBCK (TBC1-domain-containing kinase) were independently identified by whole-exome sequencing as the cause of this condition in four unrelated families. Matching these families was facilitated by the sharing of phenotypic profiles and WES data in a recently released web-based tool (Geno2MP) that links phenotypic information to rare variants in families with Mendelian traits. TBCK is a putative GTPase-activating protein (GAP) for small GTPases of the Rab family and has been shown to control cell growth and proliferation, actin-cytoskeleton dynamics, and mTOR signaling. Two of the three mutations (c.376C>T [p.Arg126(∗)] and c.1363A>T [p.Lys455(∗)]) are predicted to truncate the protein, and loss of the major TBCK isoform was confirmed in primary fibroblasts from one affected individual. The third mutation, c.1532G>A (p.Arg511His), alters a conserved residue within the TBC1 domain. Structural analysis implicated Arg511 as a required residue for Rab-GAP function, and in silico homology modeling predicted impaired GAP function in the corresponding mutant. These results suggest that loss of Rab-GAP activity is the underlying mechanism of disease. In contrast to other disorders caused by dysregulated mTOR signaling associated with focal or global brain overgrowth, impaired TBCK function results in progressive loss of brain volume.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Brain Diseases; Child; Child, Preschool; Corpus Callosum; Female; GTPase-Activating Proteins; Humans; Magnetic Resonance Imaging; Male; Molecular Sequence Data; Mutation; Pedigree; Protein Conformation; Protein-Serine-Threonine Kinases; Signal Transduction; TOR Serine-Threonine Kinases

SRD5A3-CDG: Expanding the phenotype of a congenital disorder of glycosylation with emphasis on adult onset features. - Wheeler, Patricia G; Ng, Bobby G; Sanford, Laura; Sutton, V Reid; Bartholomew, Dennis W; Pastore, Matthew T; Bamshad, Michael J; Kircher, Martin; Buckingham, Kati J; Nickerson, Deborah A; Shendure, Jay; Freeze, Hudson H (Am J Med Genet A, 2016)
Increasing numbers of congenital disorders of glycosylation (CDG) have been reported recently resulting in an expansion of the phenotypes associated with this group of disorders. SRD5A3 codes for polyprenol reductase which converts polyprenol to dolichol. This is a major pathway for dolichol biosynthesis for N-glycosylation, O-mannosylation, C-mannosylation, and GPI anchor synthesis. We present the features of five individuals (three children and two adults) with mutations in SRD5A3 focusing on the variable eye and skin involvement. We compare that to 13 affected individuals from the literature including five adults allowing us to delineate the features that may develop over time with this disorder including kyphosis, retinitis pigmentosa, and cataracts. © 2016 Wiley Periodicals, Inc.
Keywords: 3-Oxo-5-alpha-Steroid 4-Dehydrogenase; Adult; Child; Congenital Disorders of Glycosylation; Dolichols; Eye; Female; Glycosylation; Homozygote; Humans; Male; Membrane Proteins; Mutation; Phenotype; Skin; Tretinoin

Autosomal-Dominant Multiple Pterygium Syndrome Is Caused by Mutations in MYH3. - Chong, Jessica X; Burrage, Lindsay C; Beck, Anita E; Marvin, Colby T; McMillin, Margaret J; Shively, Kathryn M; Harrell, Tanya M; Buckingham, Kati J; Bacino, Carlos A; Jain, Mahim; Alanay, Yasemin; Berry, Susan A; et al. (Am J Hum Genet, 2015)
Multiple pterygium syndrome (MPS) is a phenotypically and genetically heterogeneous group of rare Mendelian conditions characterized by multiple pterygia, scoliosis, and congenital contractures of the limbs. MPS typically segregates as an autosomal-recessive disorder, but rare instances of autosomal-dominant transmission have been reported. Whereas several mutations causing recessive MPS have been identified, the genetic basis of dominant MPS remains unknown. We identified four families affected by dominantly transmitted MPS characterized by pterygia, camptodactyly of the hands, vertebral fusions, and scoliosis. Exome sequencing identified predicted protein-altering mutations in embryonic myosin heavy chain (MYH3) in three families. MYH3 mutations underlie distal arthrogryposis types 1, 2A, and 2B, but all mutations reported to date occur in the head and neck domains. In contrast, two of the mutations found to cause MPS in this study occurred in the tail domain. The phenotypic overlap among persons with MPS, coupled with physical findings distinct from other conditions caused by mutations in MYH3, suggests that the developmental mechanism underlying MPS differs from that of other conditions and/or that certain functions of embryonic myosin might be perturbed by disruption of specific residues and/or domains. Moreover, the vertebral fusions in persons with MPS, coupled with evidence of MYH3 expression in bone, suggest that embryonic myosin plays a role in skeletal development.
Keywords: Arthrogryposis; Cytoskeletal Proteins; Exome; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Mutation; Myosins; Osteogenesis

Challenges and solutions for gene identification in the presence of familial locus heterogeneity. - Rehman, Atteeq U; Santos-Cortez, Regie Lyn P; Drummond, Meghan C; Shahzad, Mohsin; Lee, Kwanghyuk; Morell, Robert J; Ansar, Muhammad; Jan, Abid; Wang, Xin; Aziz, Abdul; Riazuddin, Saima; Smith, Joshua D; et al. (Eur J Hum Genet, 2015)
Next-generation sequencing (NGS) of exomes and genomes has accelerated the identification of genes involved in Mendelian phenotypes. However, many NGS studies fall short of identifying causal variants, with estimates for success rates as low as 25% for uncovering the pathological variant underlying disease etiology. An important reason for such failures is familial locus heterogeneity, where within a single pedigree causal variants in two or more genes underlie Mendelian trait etiology. As examples of intra- and inter-sibship familial locus heterogeneity, we present 10 consanguineous Pakistani families segregating hearing impairment due to homozygous variants in two different hearing impairment genes and a European-American pedigree in which hearing impairment is caused by four variants in three different genes. We have identified 41 additional pedigrees with syndromic and nonsyndromic hearing impairment for which a single previously reported hearing impairment gene has been identified but only segregates with the phenotype in a subset of affected pedigree members. We estimate that locus heterogeneity occurs in 15.3% (95% confidence interval: 11.9%, 19.9%) of the families in our collection. We demonstrate novel approaches to apply linkage analysis and homozygosity mapping (for autosomal recessive consanguineous pedigrees), which can be used to detect locus heterogeneity using either NGS or SNP array data. Results from linkage analysis and homozygosity mapping can also be used to group sibships or individuals most likely to be segregating the same causal variants and thereby increase the success rate of gene identification.
Keywords: Asian Continental Ancestry Group; Calcium-Binding Proteins; Chromosome Mapping; Connexin 26; Connexins; Consanguinity; European Continental Ancestry Group; Female; Genes, Recessive; Genetic Heterogeneity; Genetic Linkage; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Genotype; Hearing Loss; Hepatocyte Growth Factor; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Male; Membrane Transport Proteins; Mutation; Pedigree; Phenotype; Sulfate Transporters

De novo mutations in NALCN cause a syndrome characterized by congenital contractures of the limbs and face, hypotonia, and developmental delay. - Chong, Jessica X; McMillin, Margaret J; Shively, Kathryn M; Beck, Anita E; Marvin, Colby T; Armenteros, Jose R; Buckingham, Kati J; Nkinsi, Naomi T; Boyle, Evan A; Berry, Margaret N; Bocian, Maureen; Foulds, Nicola; et al. (Am J Hum Genet, 2015)
Freeman-Sheldon syndrome, or distal arthrogryposis type 2A (DA2A), is an autosomal-dominant condition caused by mutations in MYH3 and characterized by multiple congenital contractures of the face and limbs and normal cognitive development. We identified a subset of five individuals who had been putatively diagnosed with "DA2A with severe neurological abnormalities" and for whom congenital contractures of the limbs and face, hypotonia, and global developmental delay had resulted in early death in three cases; this is a unique condition that we now refer to as CLIFAHDD syndrome. Exome sequencing identified missense mutations in the sodium leak channel, non-selective (NALCN) in four families affected by CLIFAHDD syndrome. We used molecular-inversion probes to screen for NALCN in a cohort of 202 distal arthrogryposis (DA)-affected individuals as well as concurrent exome sequencing of six other DA-affected individuals, thus revealing NALCN mutations in ten additional families with "atypical" forms of DA. All 14 mutations were missense variants predicted to alter amino acid residues in or near the S5 and S6 pore-forming segments of NALCN, highlighting the functional importance of these segments. In vitro functional studies demonstrated that NALCN alterations nearly abolished the expression of wild-type NALCN, suggesting that alterations that cause CLIFAHDD syndrome have a dominant-negative effect. In contrast, homozygosity for mutations in other regions of NALCN has been reported in three families affected by an autosomal-recessive condition characterized mainly by hypotonia and severe intellectual disability. Accordingly, mutations in NALCN can cause either a recessive or dominant condition characterized by varied though overlapping phenotypic features, perhaps based on the type of mutation and affected protein domain(s).
Keywords: Arthrogryposis; Contracture; Craniofacial Dysostosis; Cytoskeletal Proteins; Exome; Extremities; Face; Female; Gene Frequency; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Infant; Male; Muscle Hypotonia; Mutation, Missense; Sodium Channels

Expanding the Molecular and Clinical Phenotype of SSR4-CDG. - Ng, Bobby G; Raymond, Kimiyo; Kircher, Martin; Buckingham, Kati J; Wood, Tim; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Wong, Jonathan T S; Monteiro, Fabiola Paoli; Graham, Brett H; Jackson, Sheryl; et al. (Hum Mutat, 2015)
Congenital disorders of glycosylation (CDG) are a group of mostly autosomal recessive disorders primarily characterized by neurological abnormalities. Recently, we described a single CDG patient with a de novo mutation in the X-linked gene, Signal Sequence Receptor 4 (SSR4). We performed whole-exome sequencing to identify causal variants in several affected individuals who had either an undifferentiated neurological disorder or unsolved CDG of unknown etiology based on abnormal transferrin glycosylation. We now report eight affected males with either de novo (4) or inherited (4) loss of function mutations in SSR4. Western blot analysis revealed that the mutations caused a complete loss of SSR4 protein. In nearly all cases, the abnormal glycosylation of serum transferrin was only slightly above the accepted normal cutoff range.
Keywords: Calcium-Binding Proteins; Congenital Disorders of Glycosylation; DNA Mutational Analysis; Exome; Gene Order; Genes, X-Linked; Genetic Loci; Humans; Male; Membrane Glycoproteins; Mutation; Phenotype; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

A homozygous missense variant in type I keratin KRT25 causes autosomal recessive woolly hair. - Ansar, Muhammad; Raza, Syed Irfan; Lee, Kwanghyuk; Shahi, Shamim; Acharya, Anushree; Dai, Hang; Smith, Joshua D; Shendure, Jay; Bamshad, Michael J; Nickerson, Deborah A; Santos-Cortez, Regie Lyn P; Ahmad, Wasim; et al. (J Med Genet, 2015)
BACKGROUND: Woolly hair (WH) is a hair abnormality that is primarily characterised by tightly curled hair with abnormal growth. METHODS: In two unrelated consanguineous Pakistani families with non-syndromic autosomal recessive (AR) WH, homozygosity mapping and linkage analysis identified a locus within 17q21.1-q22, which contains the type I keratin gene cluster. A DNA sample from an affected individual from each family underwent exome sequencing. RESULTS: A homozygous missense variant c.950T>C (p.(Leu317Pro)) within KRT25 segregated with ARWH in both families, and has a combined maximum two-point LOD score of 7.9 at ϴ=0. The KRT25 variant is predicted to result in disruption of the second α-helical rod domain and the entire protein structure, thus possibly interfering with heterodimerisation of K25 with type II keratins within the inner root sheath (IRS) of the hair follicle and the medulla of the hair shaft. CONCLUSIONS: Our findings implicate a novel gene involved in human hair abnormality, and are consistent with the curled, fragile hair found in mice with Krt25 mutations, and further support the role of IRS-specific type I keratins in hair follicle development and maintenance of hair texture.
Keywords: Child; Child, Preschool; Consanguinity; Hair; Hair Diseases; Humans; Keratins, Type I; Male; Mutation, Missense; Pakistan; Pedigree; Sequence Analysis, DNA

Mutation of ATF6 causes autosomal recessive achromatopsia. - Ansar, Muhammad; Santos-Cortez, Regie Lyn P; Saqib, Muhammad Arif Nadeem; Zulfiqar, Fareeha; Lee, Kwanghyuk; Ashraf, Naeem Mahmood; Ullah, Ehsan; Wang, Xin; Sajid, Sundus; Khan, Falak Sher; Amin-ud-Din, Muhammad; Smith, Joshua D; et al. (Hum Genet, 2015)
Achromatopsia (ACHM) is an early-onset retinal dystrophy characterized by photophobia, nystagmus, color blindness and severely reduced visual acuity. Currently mutations in five genes CNGA3, CNGB3, GNAT2, PDE6C and PDE6H have been implicated in ACHM. We performed homozygosity mapping and linkage analysis in a consanguineous Pakistani ACHM family and mapped the locus to a 15.12-Mb region on chromosome 1q23.1-q24.3 with a maximum LOD score of 3.6. A DNA sample from an affected family member underwent exome sequencing. Within the ATF6 gene, a single-base insertion variant c.355_356dupG (p.Glu119Glyfs*8) was identified, which completely segregates with the ACHM phenotype within the family. The frameshift variant was absent in public variant databases, in 130 exomes from unrelated Pakistani individuals, and in 235 ethnically matched controls. The variant is predicted to result in a truncated protein that lacks the DNA binding and transmembrane domains and therefore affects the function of ATF6 as a transcription factor that initiates the unfolded protein response during endoplasmic reticulum (ER) stress. Immunolabeling with anti-ATF6 antibodies showed localization throughout the mouse neuronal retina, including retinal pigment epithelium, photoreceptor cells, inner nuclear layer, inner and outer plexiform layers, with a more prominent signal in retinal ganglion cells. In contrast to cytoplasmic expression of wild-type protein, in heterologous cells ATF6 protein with the p.Glu119Glyfs*8 variant is mainly confined to the nucleus. Our results imply that response to ER stress as mediated by the ATF6 pathway is essential for color vision in humans.
Keywords: Activating Transcription Factor 6; Adolescent; Animals; Asian Continental Ancestry Group; Color Vision Defects; Consanguinity; DNA Mutational Analysis; Exome; Female; Frameshift Mutation; Genotyping Techniques; Homozygote; Humans; Limit of Detection; Male; Mice; Mice, Inbred C57BL; Pakistan; Pedigree; Phenotype; Retina; Signal Transduction

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA

Attitudes of genetics professionals toward the return of incidental results from exome and whole-genome sequencing. - Yu, Joon-Ho; Harrell, Tanya M; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Hum Genet, 2014)
Professional recommendations for the return of results from exome and whole-genome sequencing (ES/WGS) have been controversial. The lack of clear guidance about whether and, if so, how to return ES/WGS incidental results limits the extent to which individuals and families might benefit from ES/WGS. The perspectives of genetics professionals, particularly those at the forefront of using ES/WGS in clinics, are largely unknown. Data on stakeholder perspectives could help clarify how to weigh expert positions and recommendations. We conducted an online survey of 9,857 genetics professionals to learn their attitudes on the return of incidental results from ES/WGS and the recent American College of Medical Genetic and Genomics Recommendations for Reporting of Incidental Findings in Clinical Exome and Genome Sequencing. Of the 847 respondents, 760 completed the survey. The overwhelming majority of respondents thought that incidental ES/WGS results should be offered to adult patients (85%), healthy adults (75%), and the parents of a child with a medical condition (74%). The majority thought that incidental results about adult-onset conditions (62%) and carrier status (62%) should be offered to the parents of a child with a medical condition. About half thought that offered results should not be limited to those deemed clinically actionable. The vast majority (81%) thought that individual preferences should guide return. Genetics professionals' perspectives on the return of ES/WGS results differed substantially from current recommendations, underscoring the need to establish clear purpose for recommendations on the return of incidental ES/WGS results as professional societies grapple with developing and updating recommendations.
Keywords: Adult; Attitude of Health Personnel; Child; Exome; Genetics, Medical; Genome, Human; Humans; Incidental Findings; Workforce

Attitudes of non-African American focus group participants toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Bamshad, Michael J; Tabor, Holly K (Am J Med Genet A, 2014)
Exome sequencing and whole genome sequencing (ES/WGS) present individuals with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, it is unclear which genetic results people want to receive (i.e., what type of genetic information they want to learn about themselves) or conversely not receive, and how they want to receive or manage results over time. Very little is known about whether and how attitudes toward receiving individual results from ES/WGS vary among racial/ethnic populations. We conducted 13 focus groups with a racially and ethnically diverse parent population (n = 76) to investigate attitudes toward return of individual results from WGS. We report on our findings for non-African American (non-AA) participants. Non-AA participants were primarily interested in genetic results on which they could act or "do something about." They defined "actionability" broadly to include individual medical treatment and disease prevention. The ability to plan for the future was both a motivation for and an expected benefit of receiving results. Their concerns focused on the meaning of results, specifically the potential inaccuracy and uncertainty of results. Non-AA participants expected healthcare providers to be involved in results management by helping them interpret results in the context of their own health and by providing counseling support. We compare and contrast these themes with those we previously reported from our analysis of African American (AA) perspectives to highlight the importance of varying preferences for results, characterize the central role of temporal orientation in framing expectations about the possibility of receiving ES/WGS results, and identify potential avenues by which genomic healthcare disparities may be inadvertently perpetuated.
Keywords: Adult; African Americans; Aged; Attitude to Health; Exome; Female; Focus Groups; Genome, Human; Humans; Male; Middle Aged; Sequence Analysis, DNA

Mutations in PIEZO2 cause Gordon syndrome, Marden-Walker syndrome, and distal arthrogryposis type 5. - McMillin, Margaret J; Beck, Anita E; Chong, Jessica X; Shively, Kathryn M; Buckingham, Kati J; Gildersleeve, Heidi I S; Aracena, Mariana I; Aylsworth, Arthur S; Bitoun, Pierre; Carey, John C; Clericuzio, Carol L; Crow, Yanick J; et al. (Am J Hum Genet, 2014)
Gordon syndrome (GS), or distal arthrogryposis type 3, is a rare, autosomal-dominant disorder characterized by cleft palate and congenital contractures of the hands and feet. Exome sequencing of five GS-affected families identified mutations in piezo-type mechanosensitive ion channel component 2 (PIEZO2) in each family. Sanger sequencing revealed PIEZO2 mutations in five of seven additional families studied (for a total of 10/12 [83%] individuals), and nine families had an identical c.8057G>A (p.Arg2686His) mutation. The phenotype of GS overlaps with distal arthrogryposis type 5 (DA5) and Marden-Walker syndrome (MWS). Using molecular inversion probes for targeted sequencing to screen PIEZO2, we found mutations in 24/29 (82%) DA5-affected families and one of two MWS-affected families. The presence of cleft palate was significantly associated with c.8057G>A (Fisher's exact test, adjusted p value < 0.0001). Collectively, although GS, DA5, and MWS have traditionally been considered separate disorders, our findings indicate that they are etiologically related and perhaps represent variable expressivity of the same condition.
Keywords: Abnormalities, Multiple; Arachnodactyly; Arthrogryposis; Blepharophimosis; Child; Child, Preschool; Cleft Palate; Clubfoot; Connective Tissue Diseases; Contracture; Exome; Female; Hand Deformities, Congenital; Humans; Ion Channels; Male; Mutation; Ophthalmoplegia; Pedigree; Retinal Diseases

Mutations in RSPH1 cause primary ciliary dyskinesia with a unique clinical and ciliary phenotype. - Knowles, Michael R; Ostrowski, Lawrence E; Leigh, Margaret W; Sears, Patrick R; Davis, Stephanie D; Wolf, Whitney E; Hazucha, Milan J; Carson, Johnny L; Olivier, Kenneth N; Sagel, Scott D; Rosenfeld, Margaret; Ferkol, Thomas W; et al. (Am J Respir Crit Care Med, 2014)
RATIONALE: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous recessive disorder of motile cilia, but the genetic cause is not defined for all patients with PCD. OBJECTIVES: To identify disease-causing mutations in novel genes, we performed exome sequencing, follow-up characterization, mutation scanning, and genotype-phenotype studies in patients with PCD. METHODS: Whole-exome sequencing was performed using NimbleGen capture and Illumina HiSeq sequencing. Sanger-based sequencing was used for mutation scanning, validation, and segregation analysis. MEASUREMENTS AND MAIN RESULTS: We performed exome sequencing on an affected sib-pair with normal ultrastructure in more than 85% of cilia. A homozygous splice-site mutation was detected in RSPH1 in both siblings; parents were carriers. Screening RSPH1 in 413 unrelated probands, including 325 with PCD and 88 with idiopathic bronchiectasis, revealed biallelic loss-of-function mutations in nine additional probands. Five affected siblings of probands in RSPH1 families harbored the familial mutations. The 16 individuals with RSPH1 mutations had some features of PCD; however, nasal nitric oxide levels were higher than in patients with PCD with other gene mutations (98.3 vs. 20.7 nl/min; P < 0.0003). Additionally, individuals with RSPH1 mutations had a lower prevalence (8 of 16) of neonatal respiratory distress, and later onset of daily wet cough than typical for PCD, and better lung function (FEV1), compared with 75 age- and sex-matched PCD cases (73.0 vs. 61.8, FEV1 % predicted; P = 0.043). Cilia from individuals with RSPH1 mutations had normal beat frequency (6.1 ± Hz at 25°C), but an abnormal, circular beat pattern. CONCLUSIONS: The milder clinical disease and higher nasal nitric oxide in individuals with biallelic mutations in RSPH1 provides evidence of a unique genotype-phenotype relationship in PCD, and suggests that mutations in RSPH1 may be associated with residual ciliary function.
Keywords: Adolescent; Adult; Child; Cilia; DNA Mutational Analysis; DNA-Binding Proteins; Exome; Female; Genetic Association Studies; Genetic Markers; Genetic Testing; Homozygote; Humans; Kartagener Syndrome; Linear Models; Male; Middle Aged; Mutation; Nasal Mucosa; Sequence Analysis, DNA; Young Adult

A new congenital disorder of glycosylation caused by a mutation in SSR4, the signal sequence receptor 4 protein of the TRAP complex. - Losfeld, Marie Estelle; Ng, Bobby G; Kircher, Martin; Buckingham, Kati J; Turner, Emily H; Eroshkin, Alexey; Smith, Joshua D; Shendure, Jay; Nickerson, Deborah A; Bamshad, Michael J; Freeze, Hudson H (Hum Mol Genet, 2014)
Nearly 50 congenital disorders of glycosylation (CDG) are known, but many patients biochemically diagnosed with CDG do not have mutations in known genes. Here, we describe a 16-year-old male who was born with microcephaly, developed intellectual disability, gastroesophageal reflux and a seizure disorder. We identified a de novo variant in the X-linked SSR4 gene which encodes a protein of the heterotetrameric translocon-associated protein (TRAP) complex. The c.316delT causes a p.F106Sfs*53 in SSR4 and also reduces expression of other TRAP complex proteins. The glycosylation marker Glyc-ER-GFP was used to confirm the underglycosylation in fibroblasts from the patient. Overexpression of the wild-type SSR4 allele partially restores glycosylation of the marker and of the other members of the TRAP complex. This is the first evidence that the TRAP complex, which binds to the oligosaccharyltransferase complex, is directly involved in N-glycosylation.
Keywords: Adolescent; Calcium-Binding Proteins; Cells, Cultured; Chromosomes, Human, X; Congenital Disorders of Glycosylation; Glycosylation; Humans; Male; Membrane Glycoproteins; Point Mutation; Receptors, Cytoplasmic and Nuclear; Receptors, Peptide

Opsismodysplasia resulting from an insertion mutation in the SH2 domain, which destabilizes INPPL1. - Li, Bing; Krakow, Deborah; Nickerson, Deborah A; Bamshad, Michael J; Chang, Yong; Lachman, Ralph S; Yilmaz, Alev; Kayserili, Hülya; Cohn, Daniel H (Am J Med Genet A, 2014)
Keywords: Adolescent; Amino Acid Sequence; Base Sequence; Child; Child, Preschool; Female; Humans; Infant; Molecular Sequence Data; Mutagenesis, Insertional; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases; Protein Stability; Radiography; RNA Splice Sites; src Homology Domains

RNF213 rare variants in an ethnically diverse population with Moyamoya disease. - Cecchi, Alana C; Guo, Dongchuan; Ren, Zhao; Flynn, Kelly; Santos-Cortez, Regie Lyn P; Leal, Suzanne M; Wang, Gao T; Regalado, Ellen S; Steinberg, Gary K; Shendure, Jay; Bamshad, Michael J; Grotta, James C; et al. (Stroke, 2014)
BACKGROUND AND PURPOSE: Moyamoya disease (MMD) is a rare, genetically heterogeneous cerebrovascular disease resulting from occlusion of the distal internal carotid arteries. A variant in the Ring Finger 213 gene (RNF213), altering arginine at position 4810 (p.R4810K), is associated with MMD in Asian populations. However, there are a lack of data on the role of RNF213 in patients with MMD of additional ethnicities and diasporic Asian populations. We investigate the contribution of RNF213 alterations to MMD in an ethnically diverse population based in the United States. METHODS: We initially sequenced RNF213 exons 43, 44, and 45 (encoding the eponymous RING finger domain) and exon 60 (encoding p.R4810K) in 86 ethnically diverse patients with MMD. Comprehensive exome sequencing data from 24 additional patients with MMD was then analyzed to identify RNF213 variants globally. Segregation of variants with MMD and other vascular diseases was assessed in families. RESULTS: RNF213 p.R4810K was identified in 56% (9/16) of patients with MMD of Asian descent and not in 94 patients of non-Asian descent. 3.6% (4/110) of patients had variants in the exons encoding the RING finger domain. Seven additional variants were identified in 29% (7/24) of patients with MMD who underwent exome sequencing. Segregation analysis supported an association with MMD for 2 variants and a lack of association with disease for 1 variant. CONCLUSIONS: These results confirm that alterations in RNF213 predispose patients of diverse ethnicities to MMD, and that the p.R4810K variant predisposes individuals of Asian descent in the United States to MMD.
Keywords: Adenosine Triphosphatases; Adolescent; Adult; Child; Cohort Studies; Ethnic Groups; Female; Genetic Variation; Humans; Male; Moyamoya Disease; Population Surveillance; Ubiquitin-Protein Ligases; Young Adult

Solving glycosylation disorders: fundamental approaches reveal complicated pathways. - Freeze, Hudson H; Chong, Jessica X; Bamshad, Michael J; Ng, Bobby G (Am J Hum Genet, 2014)
Over 100 human genetic disorders result from mutations in glycosylation-related genes. In 2013, a new glycosylation disorder was reported every 17 days. This trend will probably continue given that at least 2% of the human genome encodes glycan-biosynthesis and -recognition proteins. Established biosynthetic pathways provide many candidate genes, but finding unanticipated mutated genes will offer new insights into glycosylation. Simple glycobiomarkers can be used in narrowing the candidates identified by exome and genome sequencing, and those can be validated by glycosylation analysis of serum or cells from affected individuals. Model organisms will expand the understanding of these mutations' impact on glycosylation and pathology. Here, we highlight some recently discovered glycosylation disorders and the barriers, breakthroughs, and surprises they presented. We predict that some glycosylation disorders might occur with greater frequency than current estimates of their prevalence. Moreover, the prevalence of some disorders differs substantially between European and African Americans.
Keywords: Congenital Disorders of Glycosylation; Exome; Genome, Human; Glucose; Glycogen; Glycosylation; Homeostasis; Humans; Mannose; Mutation

TCIRG1-associated congenital neutropenia. - Makaryan, Vahagn; Rosenthal, Elisabeth A; Bolyard, Audrey Anna; Kelley, Merideth L; Below, Jennifer E; Bamshad, Michael J; Bofferding, Kathryn M; Smith, Joshua D; Buckingham, Kati; Boxer, Laurence A; Skokowa, Julia; Welte, Karl; et al. (Hum Mutat, 2014)
Severe congenital neutropenia (SCN) is a rare hematopoietic disorder, with estimated incidence of 1 in 200,000 individuals of European descent, many cases of which are inherited in an autosomal dominant pattern. Despite the fact that several causal genes have been identified, the genetic basis for >30% of cases remains unknown. We report a five-generation family segregating a novel single nucleotide variant (SNV) in TCIRG1. There is perfect cosegregation of the SNV with congenital neutropenia in this family; all 11 affected, but none of the unaffected, individuals carry this novel SNV. Western blot analysis show reduced levels of TCIRG1 protein in affected individuals, compared to healthy controls. Two unrelated patients with SCN, identified by independent investigators, are heterozygous for different, rare, highly conserved, coding variants in TCIRG1.
Keywords: DNA Mutational Analysis; Heterozygote; Humans; Mutation; Neutropenia; Pedigree; Vacuolar Proton-Translocating ATPases

Attitudes of African Americans toward return of results from exome and whole genome sequencing. - Yu, Joon-Ho; Crouch, Julia; Jamal, Seema M; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome sequencing and whole genome sequencing (ES/WGS) present patients and research participants with the opportunity to benefit from a broad scope of genetic results of clinical and personal utility. Yet, this potential for benefit also risks disenfranchising populations such as African Americans (AAs) that are already underrepresented in genetic research and utilize genetic tests at lower rates than other populations. Understanding a diverse range of perspectives on consenting for ES/WGS and receiving ES/WGS results is necessary to ensure parity in genomic health care and research. We conducted a series of 13 focus groups (n = 76) to investigate if and how attitudes toward participation in ES/WGS research and return of results from ES/WGS differ between self-described AAs and non-AAs. The majority of both AAs and non-AAs were willing to participate in WGS studies and receive individual genetic results, but the fraction not interested in either was higher in AAs. This is due in part to different expectations of health benefits from ES/WGS and how results should be managed. Our results underscore the need to develop and test culturally tailored strategies for returning ES/WGS results to AAs.
Keywords: Adult; African Americans; Aged; Attitude; Exome; Female; Focus Groups; Genetic Research; Genome-Wide Association Study; Humans; Male; Middle Aged; Sequence Analysis, DNA; Surveys and Questionnaires; Washington

Mosaicism of the UDP-galactose transporter SLC35A2 causes a congenital disorder of glycosylation. - Ng, Bobby G; Buckingham, Kati J; Raymond, Kimiyo; Kircher, Martin; Turner, Emily H; He, Miao; Smith, Joshua D; Eroshkin, Alexey; Szybowska, Marta; Losfeld, Marie E; Chong, Jessica X; Kozenko, Mariya; et al. (Am J Hum Genet, 2013)
Biochemical analysis and whole-exome sequencing identified mutations in the Golgi-localized UDP-galactose transporter SLC35A2 that define an undiagnosed X-linked congenital disorder of glycosylation (CDG) in three unrelated families. Each mutation reduced UDP-galactose transport, leading to galactose-deficient glycoproteins. Two affected males were somatic mosaics, suggesting that a wild-type SLC35A2 allele may be required for survival. In infancy, the commonly used biomarker transferrin showed abnormal glycosylation, but its appearance became normal later in childhood, without any corresponding clinical improvement. This may indicate selection against cells carrying the mutant allele. To detect other individuals with such mutations, we suggest transferrin testing in infancy. Here, we report somatic mosaicism in CDG, and our work stresses the importance of combining both genetic and biochemical diagnoses.
Keywords: Biological Transport; Case-Control Studies; Child; Child, Preschool; Congenital Disorders of Glycosylation; Exome; Female; Glycosylation; Humans; Male; Monosaccharide Transport Proteins; Mosaicism; Mutation; Spectrometry, Mass, Electrospray Ionization; Transferrin; Uridine Diphosphate Galactose

Mutations in ECEL1 cause distal arthrogryposis type 5D. - McMillin, Margaret J; Below, Jennifer E; Shively, Kathryn M; Beck, Anita E; Gildersleeve, Heidi I; Pinner, Jason; Gogola, Gloria R; Hecht, Jacqueline T; Grange, Dorothy K; Harris, David J; Earl, Dawn L; Jagadeesh, Sujatha; et al. (Am J Hum Genet, 2013)
Distal arthrogryposis (DA) syndromes are the most common of the heritable congenital-contracture disorders, and ~50% of cases are caused by mutations in genes that encode contractile proteins of skeletal myofibers. DA type 5D (DA5D) is a rare, autosomal-recessive DA previously defined by us and is characterized by congenital contractures of the hands and feet, along with distinctive facial features, including ptosis. We used linkage analysis and whole-genome sequencing of a multiplex consanguineous family to identify in endothelin-converting enzyme-like 1 (ECEL1) mutations that result in DA5D. Evaluation of a total of seven families affected by DA5D revealed in five families ECEL1 mutations that explain ~70% of cases overall. ECEL1 encodes a neuronal endopeptidase and is expressed in the brain and peripheral nerves. Mice deficient in Ecel1 exhibit perturbed terminal branching of motor neurons to the endplate of skeletal muscles, resulting in poor formation of the neuromuscular junction. Our results distinguish a second developmental pathway that causes congenital-contracture syndromes.
Keywords: Arthrogryposis; Consanguinity; Female; Genetic Linkage; Humans; Male; Metalloendopeptidases; Mutation; Sequence Analysis, DNA

Mutations in KCTD1 cause scalp-ear-nipple syndrome. - Marneros, Alexander G; Beck, Anita E; Turner, Emily H; McMillin, Margaret J; Edwards, Matthew J; Field, Michael; de Macena Sobreira, Nara Lygia; Perez, Ana Beatriz A; Fortes, Jose A R; Lampe, Anne K; Giovannucci Uzielli, Maria Luisa; Gordon, Christopher T; et al. (Am J Hum Genet, 2013)
Scalp-ear-nipple (SEN) syndrome is a rare, autosomal-dominant disorder characterized by cutis aplasia of the scalp; minor anomalies of the external ears, digits, and nails; and malformations of the breast. We used linkage analysis and exome sequencing of a multiplex family affected by SEN syndrome to identify potassium-channel tetramerization-domain-containing 1 (KCTD1) mutations that cause SEN syndrome. Evaluation of a total of ten families affected by SEN syndrome revealed KCTD1 missense mutations in each family tested. All of the mutations occurred in a KCTD1 region encoding a highly conserved bric-a-brac, tram track, and broad complex (BTB) domain that is required for transcriptional repressor activity. KCTD1 inhibits the transactivation of the transcription factor AP-2α (TFAP2A) via its BTB domain, and mutations in TFAP2A cause cutis aplasia in individuals with branchiooculofacial syndrome (BOFS), suggesting a potential overlap in the pathogenesis of SEN syndrome and BOFS. The identification of KCTD1 mutations in SEN syndrome reveals a role for this BTB-domain-containing transcriptional repressor during ectodermal development.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Branchio-Oto-Renal Syndrome; Ear, External; Ectodermal Dysplasia; Exome; Female; Humans; Hypospadias; Male; Molecular Sequence Data; Muscle Hypotonia; Mutation, Missense; Nipples; Pedigree; Phenotype; Protein Structure, Tertiary; Repressor Proteins; Scalp; Sequence Homology, Amino Acid

Practices and policies of clinical exome sequencing providers: analysis and implications. - Jamal, Seema M; Yu, Joon-Ho; Chong, Jessica X; Dent, Karin M; Conta, Jessie H; Tabor, Holly K; Bamshad, Michael J (Am J Med Genet A, 2013)
Exome and whole genome sequencing (ES/WGS) offer potential advantages over traditional approaches to diagnostic genetic testing. Consequently, use of ES/WGS in clinical settings is rapidly becoming commonplace. Yet there are myriad moral, ethical, and perhaps legal implications attached to the use of ES and health care professionals and institutions will need to consider these implications in the context of the varied practices and policies of ES service providers. We developed "core elements" of content and procedures for informed consent, data sharing, and results management and a quantitative scale to assess the extent to which research protocols met the standards established by these core elements. We then used these tools to evaluate the practices and policies of each of the 6 U.S. CLIA-certified labs offering clinical ES. Approaches toward informed consent, data sharing, and results return vary widely among ES providers as do the overall potential merits and disadvantages of each, and more importantly, the balance between the two.
Keywords: Exome; Humans; Information Dissemination; Informed Consent; Morals; Organizational Policy; Practice Patterns, Physicians'; Sequence Analysis, DNA; United States

Recurrent gain-of-function mutation in PRKG1 causes thoracic aortic aneurysms and acute aortic dissections. - Guo, Dong-Chuan; Regalado, Ellen; Casteel, Darren E; Santos-Cortez, Regie L; Gong, Limin; Kim, Jeong Joo; Dyack, Sarah; Horne, S Gabrielle; Chang, Guijuan; Jondeau, Guillaume; Boileau, Catherine; Coselli, Joseph S; et al. (Am J Hum Genet, 2013)
Gene mutations that lead to decreased contraction of vascular smooth-muscle cells (SMCs) can cause inherited thoracic aortic aneurysms and dissections. Exome sequencing of distant relatives affected by thoracic aortic disease and subsequent Sanger sequencing of additional probands with familial thoracic aortic disease identified the same rare variant, PRKG1 c.530G>A (p.Arg177Gln), in four families. This mutation segregated with aortic disease in these families with a combined two-point LOD score of 7.88. The majority of affected individuals presented with acute aortic dissections (63%) at relatively young ages (mean 31 years, range 17-51 years). PRKG1 encodes type I cGMP-dependent protein kinase (PKG-1), which is activated upon binding of cGMP and controls SMC relaxation. Although the p.Arg177Gln alteration disrupts binding to the high-affinity cGMP binding site within the regulatory domain, the altered PKG-1 is constitutively active even in the absence of cGMP. The increased PKG-1 activity leads to decreased phosphorylation of the myosin regulatory light chain in fibroblasts and is predicted to cause decreased contraction of vascular SMCs. Thus, identification of a gain-of-function mutation in PRKG1 as a cause of thoracic aortic disease provides further evidence that proper SMC contractile function is critical for maintaining the integrity of the thoracic aorta throughout a lifetime.
Keywords: Acute Disease; Adolescent; Adult; Amino Acid Sequence; Aneurysm, Dissecting; Aorta, Thoracic; Aortic Aneurysm, Thoracic; Cyclic GMP; Cyclic GMP-Dependent Protein Kinase Type I; Exome; Female; Fibroblasts; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Molecular Sequence Data; Muscle Contraction; Muscle, Smooth, Vascular; Mutation; Myosin Light Chains; Pedigree

Whole-genome analysis reveals that mutations in inositol polyphosphate phosphatase-like 1 cause opsismodysplasia. - Below, Jennifer E; Earl, Dawn L; Shively, Kathryn M; McMillin, Margaret J; Smith, Joshua D; Turner, Emily H; Stephan, Mark J; Al-Gazali, Lihadh I; Hertecant, Jozef L; Chitayat, David; Unger, Sheila; Cohn, Daniel H; et al. (Am J Hum Genet, 2013)
Opsismodysplasia is a rare, autosomal-recessive skeletal dysplasia characterized by short stature, characteristic facial features, and in some cases severe renal phosphate wasting. We used linkage analysis and whole-genome sequencing of a consanguineous trio to discover that mutations in inositol polyphosphate phosphatase-like 1 (INPPL1) cause opsismodysplasia with or without renal phosphate wasting. Evaluation of 12 families with opsismodysplasia revealed that INPPL1 mutations explain ~60% of cases overall, including both of the families in our cohort with more than one affected child and 50% of the simplex cases.
Keywords: Child; Child, Preschool; Female; Genome, Human; Humans; Infant; Infant, Newborn; Male; Mutation; Osteochondrodysplasias; Phosphatidylinositol-3,4,5-Trisphosphate 5-Phosphatases; Phosphoric Monoester Hydrolases

The Centers for Mendelian Genomics: a new large-scale initiative to identify the genes underlying rare Mendelian conditions. - Bamshad, Michael J; Shendure, Jay A; Valle, David; Hamosh, Ada; Lupski, James R; Gibbs, Richard A; Boerwinkle, Eric; Lifton, Richard P; Gerstein, Mark; Günel, Murat; Mane, Shrikant; Nickerson, Deborah A (Am J Med Genet A, 2012)
Next generation exome sequencing (ES) and whole genome sequencing (WGS) are new powerful tools for discovering the gene(s) that underlie Mendelian disorders. To accelerate these discoveries, the National Institutes of Health has established three Centers for Mendelian Genomics (CMGs): the Center for Mendelian Genomics at the University of Washington; the Center for Mendelian Genomics at Yale University; and the Baylor-Johns Hopkins Center for Mendelian Genomics at Baylor College of Medicine and Johns Hopkins University. The CMGs will provide ES/WGS and extensive analysis expertise at no cost to collaborating investigators where the causal gene(s) for a Mendelian phenotype has yet to be uncovered. Over the next few years and in collaboration with the global human genetics community, the CMGs hope to facilitate the identification of the genes underlying a very large fraction of all Mendelian disorders; see http://mendelian.org.
Keywords: Academies and Institutes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Humans

Digenic inheritance of an SMCHD1 mutation and an FSHD-permissive D4Z4 allele causes facioscapulohumeral muscular dystrophy type 2. - Lemmers, Richard J L F; Tawil, Rabi; Petek, Lisa M; Balog, Judit; Block, Gregory J; Santen, Gijs W E; Amell, Amanda M; van der Vliet, Patrick J; Almomani, Rowida; Straasheijm, Kirsten R; Krom, Yvonne D; Klooster, Rinse; et al. (Nat Genet, 2012)
Facioscapulohumeral dystrophy (FSHD) is characterized by chromatin relaxation of the D4Z4 macrosatellite array on chromosome 4 and expression of the D4Z4-encoded DUX4 gene in skeletal muscle. The more common form, autosomal dominant FSHD1, is caused by contraction of the D4Z4 array, whereas the genetic determinants and inheritance of D4Z4 array contraction-independent FSHD2 are unclear. Here, we show that mutations in SMCHD1 (encoding structural maintenance of chromosomes flexible hinge domain containing 1) on chromosome 18 reduce SMCHD1 protein levels and segregate with genome-wide D4Z4 CpG hypomethylation in human kindreds. FSHD2 occurs in individuals who inherited both the SMCHD1 mutation and a normal-sized D4Z4 array on a chromosome 4 haplotype permissive for DUX4 expression. Reducing SMCHD1 levels in skeletal muscle results in D4Z4 contraction-independent DUX4 expression. Our study identifies SMCHD1 as an epigenetic modifier of the D4Z4 metastable epiallele and as a causal genetic determinant of FSHD2 and possibly other human diseases subject to epigenetic regulation.
Keywords: Adult; Aged; Chromosomal Proteins, Non-Histone; Chromosomes, Human, Pair 18; CpG Islands; DNA Methylation; Epigenesis, Genetic; Female; Haplotypes; Heredity; Homeodomain Proteins; Humans; Male; Middle Aged; Muscular Dystrophy, Facioscapulohumeral; Mutation

Haploinsufficiency of SF3B4, a component of the pre-mRNA spliceosomal complex, causes Nager syndrome. - Bernier, Francois P; Caluseriu, Oana; Ng, Sarah; Schwartzentruber, Jeremy; Buckingham, Kati J; Innes, A Micheil; Jabs, Ethylin Wang; Innis, Jeffrey W; Schuette, Jane L; Gorski, Jerome L; Byers, Peter H; Andelfinger, Gregor; et al. (Am J Hum Genet, 2012)
Nager syndrome, first described more than 60 years ago, is the archetype of a class of disorders called the acrofacial dysostoses, which are characterized by craniofacial and limb malformations. Despite intensive efforts, no gene for Nager syndrome has yet been identified. In an international collaboration, FORGE Canada and the National Institutes of Health Centers for Mendelian Genomics used exome sequencing as a discovery tool and found that mutations in SF3B4, a component of the U2 pre-mRNA spliceosomal complex, cause Nager syndrome. After Sanger sequencing of SF3B4 in a validation cohort, 20 of 35 (57%) families affected by Nager syndrome had 1 of 18 different mutations, nearly all of which were frameshifts. These results suggest that most cases of Nager syndrome are caused by haploinsufficiency of SF3B4. Our findings add Nager syndrome to a growing list of disorders caused by mutations in genes that encode major components of the spliceosome and also highlight the synergistic potential of international collaboration when exome sequencing is applied in the search for genes responsible for rare Mendelian phenotypes.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Exome; Female; Haploinsufficiency; Humans; Limb Deformities, Congenital; Male; Mandibulofacial Dysostosis; Mutation; Reproducibility of Results; RNA Precursors; RNA Splicing Factors; RNA-Binding Proteins; Spliceosomes; Young Adult